Modified wood and transparent wood composites and systems and methods for forming and using same

By selectively removing or modifying lignin and using refractive index-matched polymer infiltration, the problem of damage to the microstructure of existing transparent wood composites when lignin is removed is solved, achieving high mechanical strength and environmentally friendly processing. process.

CN119347907APending Publication Date: 2025-01-24UNIV OF MARYLAND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411651007.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-01-07
Filing Date
2021-07-09
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Existing transparent wood composites damage the microstructure of the wood when removing lignin, resulting in a decrease in mechanical strength, and the processing process is complex and time-consuming, and commonly used delignant agents may produce toxic by-products.

Method used

Selectively remove or modify lignin through chemical treatment or UV-assisted photocatalytic oxidation treatment of continuous wood blocks, retaining part of the lignin to improve mechanical strength, and using refractive index-matched polymer infiltration to create transparent or translucent wood composite materials.

Benefits of technology

It achieves improving the mechanical strength of transparent wood composites while maintaining the integrity of the wood microstructure, simplifying the processing process, reducing the amount of chemicals used, and using environmentally friendly oxidants such as hydrogen peroxide to reduce the production of toxic by-products .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119347907A_ABST
    Figure CN119347907A_ABST
Patent Text Reader

Abstract

In some embodiments, the material comprises a continuous block of chemically modified wood infiltrated with an index matching polymer. The continuous block has a first portion that is substantially transparent to light and a second portion that is translucent or opaque. The first portion may have a lower lignin content than the second portion. Alternatively, the chromophore state of the first portion may be different from the chromophore state of the wood in its natural state, while the lignin in the second portion may maintain the chromophore state of the wood in its natural state. In some embodiments, the material includes a chemically modified wood fraction such that chromophores of lignin in the wood in its natural state are altered or removed, and the fraction retains at least 70% of the lignin of the wood in its natural state. Methods of forming such materials are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the Chinese patent application with application number 202180053907.2 and invention name “Modified wood and transparent wood composite materials and systems and methods for their formation and use”.

[0002] CROSS-REFERENCE TO RELATED APPLICATIONS

[0003] This application claims priority to U.S. Provisional Application No. 63 / 050,484, filed on July 10, 2020, entitled “Patterned, Transparent Wood and Wood Composite Structures and Methods of Making and Using the Same,” and U.S. Provisional Application No. 63 / 134,936, filed on January 7, 2021, entitled “Patterned, Transparent Wood and Wood Composite Structures and Methods of Making and Using the Same,” both of which are incorporated herein by reference in their entirety. Technical Field

[0004] The present disclosure relates generally to the processing of natural wood and, more particularly, to the formation and use of modified wood and / or transparent wood composites. Summary of the invention

[0005] Embodiments of the disclosed subject matter provide modified wood and transparent wood composite materials and methods of forming and using the same. In some embodiments, a continuous wood block is chemically treated so that the natural portion thereof undergoes different degrees of lignin removal. For example, the continuous wood block may be a softwood, and after chemical treatment, its early wood portion may be delignified, while its late wood portion may retain a large amount of lignin. The chemically treated wood block is then infiltrated with a refractive index matching polymer to convert the delignified portion into substantially transparent, while the other portions remain opaque or translucent for wavelengths in the visible light spectrum. Thus, the resulting wood composite material may present a natural pattern defined by the arrangement of the transparent early wood portion and the translucent or opaque late wood portion.

[0006] In some embodiments, continuous wood blocks are subjected to UV-assisted photocatalytic oxidation treatment to modify the lignin therein in situ, thereby converting the color of wood into white. For example, continuous wood blocks can be infiltrated with a liquid oxidant (e.g., hydrogen peroxide) and then subsequently exposed to UV radiation so that the chromophore of the lignin in the wood blocks is removed therefrom while the lignin is additionally retained in the microstructure of the wood. In some embodiments, a liquid oxidant is applied to the surface of the wood blocks and / or the wood blocks are exposed to UV light to form a pattern that limits the in-situ modification to a specific portion of the wood blocks. The in-situ modified portion is then converted to substantially transparent by infiltrating the wood blocks with a refractive index matching polymer, while the other portions remain opaque or translucent for wavelengths in the visible light spectrum. Thus, the resulting wood composite material can present a predetermined pattern defined by the application of an oxidant and UV light, regardless of any underlying natural pattern in the wood.

[0007] In a representative embodiment, the material includes a continuous block of chemically modified wood infiltrated with a polymer. The chemically modified wood can maintain the cellulose-based microstructure of the wood in its natural state. The polymer can have a refractive index that substantially matches the refractive index of cellulose and fills the open spaces within the microstructure. The continuous block can have a first portion and a second portion adjacent to the first portion. At least one of the first portion and the second portion has been chemically modified so that the lignin characteristics of the first portion are different from the lignin characteristics of the second portion. The first portion can be substantially transparent to light with a wavelength of 600nm, and the second portion can be translucent or opaque to light with a wavelength of 600nm.

[0008] In another representative embodiment, the material includes a portion of chemically modified wood so that the chromophore of the lignin in the wood under the natural state is changed or removed. The portion can retain at least 70% of the lignin in the wood in its natural state. The portion can also retain the microstructure based on cellulose in the wood in its natural state.

[0009] In another representative embodiment, a method includes chemically treating a continuous wood block for a first time to remove lignin from a first portion and a second portion within the continuous block while substantially maintaining the cellulose-based microstructure of the wood. The first portion may be adjacent to the second portion. The first time may be selected so that at least 90% of the lignin of the wood in the first portion is removed, while less than 75% (e.g., no more than 65%, or no more than 50%) of the lignin in the second portion is removed. The method may also include infiltrating the continuous block with a polymer to fill the open spaces within the retained cellulose-based microstructure of the first portion and the second portion. The polymer may have a refractive index that substantially matches the refractive index of cellulose. After infiltration, the first portion may be substantially transparent to light with a wavelength of 600nm, and the second portion may be translucent to light with a wavelength of 600nm.

[0010] In another representative embodiment, a method includes applying a first volume of a liquid oxidant to an outer surface of a portion of a continuous wood block, and during or after the application, exposing the portion of the continuous wood block to ultraviolet (UV) radiation. In the presence of the liquid oxidant, chromophores of lignin within the portion can be chemically oxidized and removed in situ by UV exposure. After exposure, at least 70% of the lignin in the portion before application is retained. After exposure, the portion can also retain the cellulose-based microstructure of the wood before application.

[0011] In another representative embodiment, a method includes photocatalytically oxidizing a portion of a continuous wood block to chemically modify in situ native lignin within the portion to remove its chromophores while retaining its bulk aromatic backbone.

[0012] Any of the various innovations disclosed herein may be used in combination or alone. This summary is provided to introduce a selection of concepts in a simplified form, which concepts will be further described in the detailed description below. This summary is not intended to specify key features or essential features of the claimed subject matter, nor is it intended to be used to limit the scope of the claimed subject matter. The foregoing and other objects, features, and advantages of the disclosed technology will become more apparent through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Embodiments will be described below with reference to the accompanying drawings, which are not necessarily drawn to scale. Where applicable, some elements may be simplified or otherwise not shown to assist in illustrating and describing essential features. In all the accompanying drawings, the same reference numerals represent the same elements.

[0014] Figure 1A is a simplified process flow diagram of a general manufacturing method for forming a modified wood or transparent wood composite material according to one or more embodiments of the disclosed subject matter.

[0015] Figure 1B-1D is a simplified process flow diagram of an alternative subroutine for forming a modified wood or transparent wood composite material according to one or more embodiments of the disclosed subject matter.

[0016] Figure 2A Shown are radial, longitudinal, and rotational cuts of natural wood that may be used to form modified wood or transparent wood composites according to one or more embodiments of the disclosed subject matter.

[0017] Figure 2B is a simplified cross-sectional view showing the microstructure of natural wood comprising cellulose-based longitudinal units.

[0018] Figure 2C is a photo of a continuous piece of natural wood with different parts before processing.

[0019] Figure 2D is a simplified schematic diagram showing the different earlywood and latewood parts in natural wood.

[0020] Figure 2E It is a scanning electron microscope (SEM) image of a cross section of the earlywood and latewood parts of natural wood along a direction perpendicular to the longitudinal wood growth direction.

[0021] Figure 3A is a simplified schematic diagram showing different earlywood and latewood fractions in a continuous piece of wood composite material after chemical delignification and polymer infiltration, according to one or more embodiments of the disclosed subject matter.

[0022] Figure 3B are SEM images of cross sections of earlywood and latewood parts in transparent wood composites after chemical delignification and polymer infiltration along a direction perpendicular to the longitudinal wood growth direction.

[0023] Figure 3C are photographs of successive pieces of the naturally patterned transparent wood composite after processing.

[0024] Figures 4A-4B An exemplary batch manufacturing facility and an exemplary continuous or semi-continuous manufacturing facility for forming a natural patterned transparent wood composite material according to one or more embodiments of the disclosed subject matter are shown, respectively.

[0025] Figure 4C is a perspective view of an exemplary quarter-slicing cutting arrangement that may be used in a manufacturing facility according to one or more embodiments of the disclosed subject matter.

[0026] Figure 5Ais a schematic diagram illustrating photocatalytic chemical oxidation and resulting in-situ structural changes of lignin within wood according to one or more embodiments of the disclosed subject matter.

[0027] Figure 5B An exemplary batch manufacturing process for forming modified wood or transparent wood composites by patterned application of a chemical oxidant (eg, hydrogen peroxide) according to one or more embodiments of the disclosed subject matter is shown.

[0028] Figure 5C Exemplary batch manufacturing for forming modified wood or transparent wood composites by patterned exposure to ultraviolet radiation according to one or more embodiments of the disclosed subject matter is shown.

[0029] Figure 5D An exemplary batch manufacturing for forming a modified wood or transparent wood composite material without any patterning is shown according to one or more embodiments of the disclosed subject matter.

[0030] Figure 6 An exemplary continuous or semi-continuous manufacturing facility for forming a modified wood or transparent wood composite material according to one or more embodiments of the disclosed subject matter is shown.

[0031] Fig. 7A is a SEM image of the cellulose-based microstructure of Douglas fir at the boundary between earlywood and latewood parts.

[0032] Figure 7B-7C They are Fig. 7A Magnified SEM images of the earlywood and latewood parts of natural Douglas fir.

[0033] Fig.7D yes Fig. 7A SEM of a longitudinal cross section of a Douglas-fir tracheid.

[0034] Figure 7E-7F The pore size distribution of the earlywood and latewood parts of natural Douglas fir are shown respectively.

[0035] Figure 7G Raman spectra of cell wall components of earlywood and latewood parts in natural Douglas fir and fabricated natural patterned transparent wood composites are shown, respectively.

[0036] Figure 7H Shown are Raman spectra of cell wall components in the fabricated natural patterned transparent wood composite.

[0037] Fig.7I is a graph of the transmittance of the earlywood part and the latewood part in the fabricated natural patterned transparent wood composite at 600 nm.

[0038] Figure 7J are plots of absorbance, transmittance, and reflectance spectra of continuous pieces of fabricated natural patterned transparent wood composites.

[0039] Figure 7K is a graph of the UV blocking properties of fabricated successive pieces of natural patterned transparent wood composites based on the duration of the delignification treatment.

[0040] Figure 7L is a graph of the haze of fabricated continuous pieces of natural patterned transparent wood composites.

[0041] Figure 7M Individual sequential pieces of the naturally patterned transparent wood composite are shown assembled to form a customized pattern.

[0042] Fig. 8A is a plot of normalized lignin content versus treatment time after photocatalytic oxidation treatment to form lignin-modified wood in situ.

[0043] Figure 8B are Fourier transform infrared (FTIR) spectra of manufactured contiguous pieces of natural wood and in situ lignin modified wood.

[0044] Figure 8C are X-ray diffraction (XRD) spectra of manufactured contiguous pieces of natural wood and in situ lignin-modified wood.

[0045] Fig.8D are X-ray photoelectron spectroscopy (XPS) spectra of fabricated contiguous pieces of natural wood and in situ lignin-modified wood.

[0046] Fig. 8E are the reflectance spectra at different positions of the fabricated continuous pieces of in situ lignin-modified wood.

[0047] Figure 8F Shown are macro-scale and micro-scale images comparing fabricated continuous pieces of in situ lignin-modified wood (eg, photo-modified wood) and fabricated delignified wood pieces.

[0048] Figure 8G-8H are images of successive pieces of fabrication of in situ lignin modified wood pieces with customized patterns.

[0049] Figures 9A-9B Plots of FTIR spectra and lignin content of natural wood, fabricated continuous pieces of in-situ lignin modified wood and fabricated continuous pieces of transparent wood composites, respectively.

[0050] Figures 9C-9E SEM images of cross sections of the fabricated continuous pieces of natural wood, in-situ lignin modified wood, and transparent wood composites, respectively.

[0051] Figure 9F-9G Plots comparing the transmittance and absorbance spectra of longitudinal (L) and radial (T) cut pieces of natural wood and transparent wood composites, respectively.

[0052] Figure 9H is a haze graph of a manufactured continuous piece of a transparent wood composite formed from longitudinal (L) and radial (T) cuts of natural wood.

[0053] Fig.9I is an image of a fabricated continuous piece of transparent wood composite material with a custom pattern. Specific implementation plan

[0054] General Considerations

[0055] For the purpose of this description, certain aspects, advantages and novel features of the embodiments of the present disclosure are described herein. The disclosed methods and systems should not be construed as limiting in any way. On the contrary, the present disclosure relates to all novel and non-obvious features and aspects of the various disclosed embodiments, individually and in various combinations and sub-combinations of each other. The methods and systems are not limited to any particular aspect or feature or combination thereof, nor do the disclosed embodiments require the presence of any one or more specific advantages or problems solved. The technology from any embodiment or embodiment can be combined with the technology described in any one or more other embodiments or embodiments. In view of the many possible embodiments to which the principles of the disclosed technology can be applied, it should be recognized that the illustrated embodiments are exemplary only and should not be considered to limit the scope of the disclosed technology.

[0056] Although the operations of some disclosed methods are described in a particular order for ease of presentation, it should be understood that this description encompasses rearrangement unless specific language is given below requiring a particular order. For example, in some cases, the operations described in sequence may be rearranged or performed simultaneously. In addition, for simplicity, the accompanying drawings may not show the various ways in which the disclosed methods can be used in conjunction with other methods. In addition, the specification sometimes uses terms such as "providing" or "implementing" to describe the disclosed methods. These terms are high-level abstractions of the actual operations performed. The actual operations corresponding to these terms may vary depending on the specific implementation, and are easily discernible by those of ordinary skill in the art.

[0057] Unless otherwise stated, the disclosed numerical ranges should be understood to refer to each discrete point within the range, including endpoints. Unless otherwise stated, all numbers used in the specification or claims to indicate the number of components, molecular weight, percentage, temperature, time, etc. should be understood to be modified by the term "about". Therefore, unless otherwise implied or explicitly indicated, or unless a person of ordinary skill in the art correctly understands the context and thus has a clearer interpretation, the numerical parameters are approximate values, which may depend on the desired properties and / or detection limits sought under standard test conditions / methods, as known to those of ordinary skill in the art. When the embodiment is directly and clearly distinguished from the prior art discussed, the numerical value of the embodiment is not approximate unless the word "about" is recorded. When "substantially", "approximately", "about" or similar language is used in explicit combination with a specific value, changes within 10% (including 10%) of the value should be considered, unless otherwise explicitly stated.

[0058] Directional and other relative references may be used to assist in the discussion of the drawings and principles herein, but are not intended to be limiting. For example, certain terms such as "interior," "exterior," "upper," "lower," "top," "bottom," "inside," "outside," "left," "right," "front," "rear," "rear," etc. may be used. When dealing with relative relationships, particularly with respect to the illustrated embodiments, such terms are used to provide some clarity of description where applicable. However, these terms do not imply absolute relationships, positions, and / or directions. For example, for an object, a "upper" portion may become a "lower" portion simply by flipping the object. However, it is still the same portion and the object remains unchanged.

[0059] As used herein, "comprising" means "including", and the singular forms "a", "an", or "the" include plural references unless the context clearly indicates otherwise. The term "or" refers to a single element or a combination of two or more elements of the alternative elements, unless the context clearly indicates otherwise.

[0060] Although there are alternatives for various components, parameters, operating conditions, etc. described herein, this does not mean that these alternatives are necessarily equivalent and / or equivalent in performance. Unless otherwise stated, this does not mean that the alternatives are listed in a preferred order. Unless otherwise stated, any group defined below may be substituted or unsubstituted.

[0061] Unless otherwise explained, all technical terms and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present disclosure belongs. Although methods and materials similar or equivalent to the methods and materials described herein can be used for the practice or testing of the present disclosure, suitable methods and materials are described below. Materials, methods and embodiments are merely illustrative and are not intended to be limiting. The features of the present disclosure theme will be apparent from the following detailed description and the appended claims.

[0062] Terminology Overview

[0063] The following explanations of specific terms and abbreviations are provided to facilitate describing various aspects of the disclosed subject matter and to guide those of ordinary skill in the art in practicing the disclosed subject matter.

[0064] Continuous piece: A continuous piece of wood taken from a tree and processed, as opposed to a single piece formed by connecting or combining multiple sub-pieces (e.g., laminating). In some embodiments, the processing forms portions or regions with different lignin characteristics within the continuous wood piece.

[0065] Lignin characteristics: In some embodiments, lignin characteristics refer to the content of naturally occurring or natural lignin in a wood part. Thus, different lignin characteristics can refer to the natural lignin content of one wood part after processing is less than the lignin content of an adjacent wood part (e.g., such that an earlywood region is substantially delignified, while an adjacent latewood region retains most or at least some natural lignin). Alternatively or in addition, in some embodiments, lignin characteristics refer to naturally occurring or natural form lignin in a wood part. Thus, different lignin characteristics can refer to a wood part in which natural lignin is in situ modified (e.g., by chemical oxidation) to change or remove chromophores of lignin without removing lignin, while an adjacent wood part retains lignin in natural form after processing.

[0066] Delignification is a wood part, at least 90% of the natural lignin originally in the wood part is removed therefrom. In some embodiments, the lignin content of the delignified wood part does not exceed 3wt%, such as less than 1wt%. The lignin content in the cellulose-based material before and after delignification can be evaluated using techniques known in the art, for example, Laboratory Analytical Procedure (LAP) TP-510-42618, "Determination of Structural Carbohydrates and Lignin in Biomass", published by the National Renewable Energy Laboratory (NREL), March 8, 2012, and ASTM E1758-01 (2020), "Standard Test Method for Determination of Carbohydrates in Biomass by High Performance Liquid Chromatography", published by ASTM International, both of which are incorporated herein by reference.

[0067] Longitudinal growth direction: The direction in which a plant grows from its roots or from its trunk, and the cellulose nanofibers that form the plant cell wall are usually aligned with the longitudinal growth direction. In some cases, the longitudinal growth direction is usually vertical, or corresponds to the direction of its transpiration water flow. This is opposite to the radial direction, which extends outward from the central part of the plant and is usually horizontal.

[0068] Transparent: Having a transmittance value (ie, the ratio of the intensity of transmitted light to the intensity of incident light) of at least 80% for a specific wavelength of light or range of wavelengths of light.

[0069] Translucent Having a transmittance value between 36% and 80% for a specific wavelength or range of wavelengths of light.

[0070] Opaque: For a specific wavelength or range of wavelengths of light, the transmittance value is less than 36%.

[0071] introduceTransparent wood composites with improved mechanical properties can be formed by retaining some or all of the lignin naturally present in the initial wood material. In existing transparent wood composites, it is necessary to remove most or all (e.g., at least 90%) of the lignin in the initial wood to obtain high transparency (e.g., for visible light wavelengths, >80%). However, removing such a large amount of lignin will compromise the integrity of the wood's cellulose-based microstructure, thereby complicating subsequent manufacturing steps (e.g., polymer infiltration) and compromising the resulting mechanical strength of the composite.

[0072] In some embodiments of the disclosed subject matter, a continuous wood block can be chemically treated so that the natural portion thereof undergoes different degrees of lignin removal. For example, the continuous wood block can be a softwood, and after chemical treatment, its early wood portion can be delignified, while its late wood portion can retain a large amount of lignin. The chemically treated wood block is then infiltrated with a refractive index matching polymer to convert the delignified portion into a substantially transparent portion, while the other portions remain opaque or translucent for wavelengths in the visible light spectrum. Therefore, the resulting wood composite material can present a natural pattern defined by the arrangement of the transparent early wood portion and the translucent or opaque late wood portion. In addition, since the late wood portion retains a large amount of lignin, the overall mechanical strength of the material is improved compared to a fully delignified wood composite material.

[0073] Alternatively or in addition, in some embodiments of the disclosed subject matter, a continuous wood block is subjected to UV-assisted photocatalytic oxidation treatment to modify the lignin therein in situ, thereby converting the color of the wood to white. For example, a continuous wood block can be infiltrated with a liquid oxidant (such as hydrogen peroxide) and then subsequently exposed to UV radiation so that the lignin chromophores in the wood block are removed therefrom, while the lignin is retained in the microstructure of the wood. In some embodiments, applying a liquid oxidant to the surface of the wood block and / or exposing the wood block to UV light can form a pattern that limits the in-situ modification to a specific portion of the wood block. The wood block is then infiltrated with a refractive index matching polymer to convert the in-situ modified portion to be substantially transparent, while other portions remain opaque or translucent for wavelengths in the visible light spectrum. Thus, the resulting wood composite material can present a predetermined pattern defined by the application of the oxidant and UV light, regardless of any underlying natural pattern in the wood. Since the photocatalytic oxidation treatment does not remove lignin or removes only minimal lignin (eg, less than 30% of the lignin in the original wood), the overall mechanical strength of the material is improved compared to fully delignified wood composites.

[0074] In addition, existing transparent wood composites require large amounts of chemicals and a large amount of processing time to delignify the wood, which may reduce manufacturability. In contrast, in some embodiments, a UV-assisted photocatalytic oxidation process is used to process the wood to modify the lignin therein in situ by surface application of a liquid oxidant. Therefore, the processing time and the amount of chemicals used can be reduced compared to existing transparent wood processing. In addition, the use of hydrogen peroxide (H2O2) as a liquid oxidant provides a more environmentally friendly process compared to delignifying agents (such as NaClO2) that can release toxic chlorine gas, because H2O2 only produces water or oxygen as a byproduct.

[0075] In some embodiments, a naturally patterned transparent wood composite material (also referred to as aesthetic wood) is provided. The aesthetic wood can have aesthetic features (e.g., a complete wood pattern), excellent optical properties (e.g., an average transmittance of about 80% and a haze of about 93%), good UV blocking ability (e.g., a transmittance of ≤20%), and low thermal conductivity (0.24 W·m 2 ) based on a spatially selective delignification and refractive index matching polymer (e.g., epoxy resin) infiltration process. -1 K -1 In addition, the rapid manufacturing process (e.g., chemical treatment in 2 h or less) and mechanical strength (e.g., high longitudinal tensile strength of 91.95 MPa and 2.73 MJ·m -3 The toughness of wood can be achieved on a large scale, while saving a lot of time and energy. For example, aesthetic wood can be used in energy-saving building applications such as glass ceilings, roofs, transparent decoration and interior panels.

[0076] In some embodiments, modified wood (also referred to as in-situ lignin modified wood, lignin modified wood or photosensitive wood) is provided. Lignin in natural wood can be modified using an in-situ, rapid and scalable method, particularly by photocatalytic oxidation of natural lignin in wood using a liquid oxidant (e.g., hydrogen peroxide) and ultraviolet light (e.g., solar radiation or artificial lighting in the UVA band). The photocatalytic oxidation reaction selectively eliminates the chromophores of lignin while keeping the aromatic skeleton of lignin intact, thereby adjusting the optical properties of wood. The resulting photosensitive wood retains about 80% of its initial lignin content, which will continue to be used as a strong adhesive and waterproofing agent. As a result, compared with the delignification of wood, photosensitive wood exhibits much higher mechanical strength (e.g., 20 times higher tensile strength and 12 times higher compressive strength), significant scalability (e.g., about 2 meters long sample) and greatly reduced processing time (e.g., 1 to 6.5 hours compared to 4 to 14 hours) in a humid environment. Furthermore, in situ lignin-modified wood structures can be patterned using photocatalytic oxidation processes, specifically by selectively applying liquid oxidants or UV radiation to the wood surface. This photocatalytic production of photoactivated wood could enable large-scale manufacturing of sustainable, bio-sourced functional materials for a range of applications, including energy-efficient buildings, light management, and fluid, ionic, electronic, and optical devices.

[0077] In some embodiments, a transparent wood composite material (also referred to as an in-situ lignin-modified transparent wood composite material, an artificially patterned transparent wood composite material, or simply transparent wood) is provided. Similar to photosensitive wood, lignin in natural wood can be modified using ultraviolet-assisted photocatalytic oxidation. This retains most of the natural lignin as a binder, thereby providing a solid wood support for polymer infiltration, while greatly reducing chemical and energy consumption and processing time. After polymer infiltration, the resulting transparent wood (e.g., with a thickness of about 1 mm) can exhibit high transmittance (e.g., >90%), high haze (e.g., >60%), and excellent light-guiding effect for visible light wavelengths. In addition, similar to photosensitive wood, patterns can be formed directly on the wood surface by selectively applying a liquid oxidant (e.g., brushing or printing) or UV radiation (e.g., mask or laser irradiation). Compared with delignified wood (e.g., a tensile strength of 0.4 MPa), lignin-modified wood has a significantly higher tensile strength (e.g., 20.6 MPa) due to the presence of modified lignin combined with well-oriented cellulose fibrils.

[0078] Method Embodiment

[0079] Figure 1AAn exemplary method 100 for forming a modified wood or transparent wood composite is shown. The method 100 can begin with a processing frame 102, in which a continuous piece 101 of natural wood is prepared. For example, the preparation of the processing frame 102 may include cutting, removing, or otherwise separating the wood piece from the parent tree. In some embodiments, the cutting can form the natural wood into a substantially flat planar structure, with the direction of the cellulose fibers extending parallel to the plane of the structure (e.g., longitudinal cutting or rotary cutting) or perpendicular to the plane of the structure (e.g., radial cutting). Optionally, in some embodiments, the preparation can include pre-treating the natural wood piece, for example, cleaning to remove any undesirable materials or contaminants in the preparation for subsequent processing, forming the natural cellulose-based material into a specific shape in the preparation for subsequent processing (e.g., slicing into strips), or any combination of the foregoing. In some embodiments, the continuous piece 101 of natural wood can be a softwood, in which well-defined natural portions have different characteristics such as an earlywood (EW) region 103 and an adjacent latewood (LW) region 105. Alternatively, in some embodiments, the continuous piece of natural wood 101 may be hardwood or softwood, without a clearly defined natural portion.

[0080] In processing block 104, the continuous piece of natural wood may be subjected to one or more chemical-based treatments to modify the lignin characteristics of at least a portion of the wood piece. In some embodiments, the lignin characteristics are modified such that at least one portion is formed to have a different lignin characteristic than an adjacent portion. For example, in some embodiments, the lignin characteristic is the lignin content of a portion of the continuous piece of processed wood 107, and the chemical-based treatment may cause the lignin content of one wood portion 109 (e.g., the former EW region 103) to be less than the lignin content of an adjacent wood portion 111 (e.g., the former LW region 105), as described below with respect to Figure 1B Alternatively, in some embodiments, the lignin characteristic is the presence of chromophores, and the chemical-based treatment may result in the removal of chromophores in one wood portion 109 while the chromophores in an adjacent wood portion 111 are retained, as described below with respect to Figure 1C-1D Alternatively, in some embodiments, the lignin characteristics are modified such that an entire continuum is formed that has the characteristics of lignin (eg, lignin content or the presence of chromophores).

[0081] The method 100 may proceed to decision block 106 where it is determined whether a transparent composite material is desired. If it is determined that a transparent composite material is not desired, e.g., for use as photopolymerizable wood, the method 100 may proceed from decision block 106 to processing block 110. Otherwise, if it is determined that a transparent composite material is desired, the method 100 may proceed from decision block 106 to processing block 108 where the wood continuum is infiltrated with a refractive index matching polymer to modify the wood continuum.

[0082] In some embodiments, the polymer infiltration of processing box 108 can be accomplished by one or more vacuum-assisted infiltration processes, for example, by immersing the modified wood in a container of a liquid polymer or polymer precursor and applying a vacuum to a chamber containing the container, or as described in International Publication No. WO-2017 / 136714 filed on February 3, 2017, which is incorporated herein by reference. The polymer can be any polymer that has a refractive index that is substantially matched to cellulose (e.g., having a refractive index of about 1.47) and is capable of infiltrating into the wood microstructure. For example, the infiltrating refractive index matching polymer can include any type of thermosetting polymer (e.g., epoxy resin), thermoplastic polymer (e.g., acrylic), cellulose derivative (e.g., cellulose acetate), and / or functional refractive index matching material (e.g., liquid crystal or piezoelectric material). Non-limiting examples of polymers that can be infiltrated into the modified wood can include, but are not limited to, those described in International Publication No. WO-2017 / 136714, incorporated herein by reference. In some embodiments, the polymer can be an epoxy resin (eg, AeroMarine 300 / 21 epoxy resin).

[0083] In some embodiments, processing frame 110 may also include drying or polymerizing the infiltrated precursor. In some embodiments, the wood modified with the infiltrated polymer is pressed during the drying or polymerization process. For example, when the first portion 109 has been delignified in processing frame 104 and the second portion 111 retains lignin, the different mechanical strengths of the portions may result in warping when the polymer is dried or polymerized in these portions. Therefore, a nominal pressure (e.g., where the thickness of the continuous piece does not change by more than 10%) may be applied during the drying or polymerization process to prevent or at least reduce any warping.

[0084] Thus, penetration of the polymer by processing block 110 may convert some or all of the wood portions to be substantially transparent. For example, when wood portion 109 is substantially delignified or de-chromophoresed by chemical treatment at processing block 104, the infiltrating polymer may convert portion 109 to substantially transparent portion 115. At the same time, when wood portion 111 retains lignin and its chromophores after chemical treatment at the processing block, portion 111 remains a translucent or opaque portion 117 after polymer infiltration. Alternatively, in some embodiments, when an entire continuous piece 107 having modified lignin properties is formed, then after polymer infiltration, the entire piece 113 will become transparent.

[0085] After polymer infiltration at processing block 108, or if polymer infiltration is not required at decision block 106, method 100 may proceed to processing block 110, where the modified wood or transparent wood composite is used in or adapted for a particular application. For example, processing block 110 may include processing, cutting, or otherwise forming the continuous piece into a particular shape. Use of processing block 110 may include using the continuous piece of modified wood or transparent wood composite material by itself or assembling it with non-wood materials (e.g., metals, metal alloys, plastics, ceramics, composite materials, etc.) to form a heterogeneous composite structure. In some embodiments, after polymer infiltration at processing block 108, the continuous piece of transparent wood composite material may be used as a part of a building (e.g., a window or skylight). Alternatively, in some embodiments, when a transparent composite material is not desired at decision block 106, the continuous piece of modified wood may be used as an insulating structure or a visible light reflector. Other applications other than those specifically listed are possible for modified wood and transparent wood composite structures made according to the disclosed technology. In fact, one of ordinary skill in the art will readily appreciate that, based on the teachings of the present disclosure, the modified wood and transparent wood composite structures disclosed herein may be suitable for other applications.

[0086] Although some of the blocks 102-110 of the method 100 have been described as being performed once, in some embodiments, multiple repetitions of a particular processing block may be employed before proceeding to the next decision block or processing block. Furthermore, although the blocks 102-110 of the method 100 have been shown and described separately, in some embodiments, the processing blocks may be combined and performed together (either simultaneously or sequentially). Furthermore, although Figure 1A The specific order of blocks 102-110 is shown, but the embodiments of the disclosed subject matter are not limited thereto. In fact, in some embodiments, the blocks may occur in a different order than shown, or may occur simultaneously with other blocks.

[0087] Figure 1B Shown can be used Figure 1AA first exemplary subroutine 104a of a chemical-based treatment of the processing frame 104 of the method 100 of the present invention is provided. For example, the subroutine 104a can be used to form a natural patterned transparent wood composite material based on the selective delignification of the EW and LW fractions naturally present in softwood (e.g., pine, cedar, spruce, larch, or fir). The subroutine 104a can begin with the processing frame 112, in which the continuous pieces of natural wood are immersed in one or more chemical solutions to remove lignin from the wood. The physical properties of the EW fraction (e.g., lower density, larger lumen size, thinner cell wall) compared to the LW fraction (e.g., higher density, smaller lumen size, thicker cell wall) cause the chemical solution to more easily penetrate the EW fraction and react with the EW fraction, so that the lignin is removed from the EW fraction faster than the LW fraction. By appropriately timing the chemical treatment of the processing frame 112, the EW fraction and the LW fraction can be processed to have different lignin contents. In particular, once the EW fraction is delignified or shortly thereafter, by terminating the chemical treatment (eg, by removing the continuum from solution), the LW fraction may retain a significant amount of lignin.

[0088] In some embodiments, the chemical treatment of processing frame 112 can be carried out under vacuum so as to promote complete penetration of the cell walls and lumens of the continuous wood pieces by the solution associated with the treatment. Alternatively, in some embodiments, the chemical treatment of processing frame 112 can be carried out under ambient pressure conditions or elevated pressure conditions (e.g., about 6 to 8 bars). In some embodiments, the chemical treatment of processing frame 112 can be carried out at any temperature between ambient temperature (e.g., about 23° C.) and an elevated temperature (e.g., about 70 to 160° C.) at which the chemical solution boils. In some embodiments, the chemical solution is not stirred to avoid damaging the cellulose-based microstructure of the wood. In some embodiments, the chemical solution can include sodium chlorite (NaClO2) alone or in combination with other chemicals (e.g., acetic acid). For example, in some embodiments, the chemical solution includes a boiling solution of NaClO2.

[0089] In some embodiments, the soaking time can be less than 5 hours, for example 2 hours or shorter. The amount of time soaked in the chemical solution can be a function of the amount of lignin to be removed, the size of the workpiece, the density of the EW part, the temperature of the solution, the pressure of the treatment and / or the stirring. For example, a smaller amount of lignin removal, a smaller workpiece size, a lower density of the EW part, a higher solution temperature, a higher treatment pressure and stirring can be associated with a shorter soaking time, while a larger amount of lignin removal, a larger workpiece size, a higher density of the EW part, a lower solution temperature, a lower treatment pressure and no stirring may be associated with a longer soaking time.

[0090] At decision block 114, it is determined whether the treatment of process block 112 should continue. Treatment with the chemical solution may continue (or may be repeated with subsequent solutions) until a desired reduction in lignin content in the EW portion is achieved, e.g., a desired light transmittance is achieved after infiltration with the refractive index matching polymer at process block 108. In some embodiments, treatment of process block 112 continues until the lignin content in the EW portion is reduced by at least 90% (e.g., less than 10% of the initial lignin in the EW portion remains), which may correspond to a light transmittance of at least 80% for one or more wavelengths in the visible light spectrum (e.g., 600 nm). For example, after treatment of process block 112, the EW portion may have a lignin content of less than or equal to 3 wt%, e.g., less than or equal to 1 wt%. In some embodiments, the processing of processing block 112 can be effective to reduce the lignin content in the LW portion by no more than 75% (e.g., retaining more than 25% of the initial lignin in the LW portion), for example, by no more than 65%, or even by no more than 50%, which can correspond to a transmittance of less than 70% for one or more wavelengths in the visible light spectrum (e.g., 600 nm). For example, after processing of processing block 112, the LW portion can have a lignin content greater than or equal to 7.5 wt%, such as greater than or equal to 12.5 wt%.

[0091] Once enough lignin has been removed from the EW part, subroutine 104a can proceed from decision box 114 to processing box 116, in which the continuous piece of modified wood is removed from the chemical solution to prepare for polymer infiltration at processing box 108. In some embodiments, processing box 116 can further include an optional rinsing step after chemical treatment, for example, to remove residual chemicals or particles produced in the delignification process. For example, the continuous piece of modified wood can be partially or completely immersed in one or more rinsing solutions. The rinsing solution can be a solvent, such as but not limited to deionized (DI) water, alcohol (e.g., ethanol, methanol, isopropanol, etc.), or any combination thereof. For example, the rinsing solution can be formed by water and ethanol. In some embodiments, for each repetition, a fresh mixture rinsing solution can be used to repeatedly rinse multiple times (e.g., at least 3 times). In some embodiments, after rinsing, the continuous piece can be stored in an alcohol (e.g., ethanol). In some embodiments, after storage, and prior to polymer infiltration at process block 108, the continuous piece may be immersed in another solvent (eg, toluene) to exchange the alcohol therein.

[0092] Although some of the blocks 112-116 of the subroutine 104a have been described as being performed once, in some embodiments, multiple repetitions of a particular processing block may be employed before proceeding to the next decision block or processing block. Furthermore, although the blocks 112-116 of the subroutine 104a have been shown and described separately, in some embodiments, the processing blocks may be combined and performed together (simultaneously or sequentially). Furthermore, although Figure 1B The specific order of blocks 112-116 is shown, but the embodiments of the disclosed subject matter are not limited thereto. In fact, in some embodiments, the blocks may occur in a different order than shown, or may occur simultaneously with other blocks.

[0093] Figure 1C Shown can be used for Figure 1A A second exemplary subroutine 104b of a chemical-based treatment of processing frame 104 of method 100 is provided. For example, subroutine 104b can be used to form a continuous piece of patterned in-situ lignin modified wood or a patterned transparent wood composite. Subroutine 104b can begin with optional processing frame 118, in which a contour of a predetermined pattern is formed on the upper exposed surface of the continuous piece of wood to delineate adjacent first and second portions within the wood. For example, the contour can be formed using a hydrophobic material such as petroleum jelly. The contour can effectively prevent a liquid oxidant (e.g., hydrogen peroxide) from flowing from the first portion to the second portion (or vice versa) when subsequently applied to the surface. However, in some embodiments, for example, when the liquid oxidant is applied in a manner to avoid or at least reduce lateral diffusion to adjacent portions, the contour can be omitted. In some embodiments, the predetermined pattern can define a plurality of first portions separated from each other by one or more intermediate second portions.

[0094] Subroutine 104b may proceed to optional processing block 120, in which a first volume of an alkaline solution is applied to an upper exposed surface portion of the continuous piece corresponding to the first portion. For example, the alkali may be sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), calcium hydroxide (Ca(OH)2), or any combination thereof. In some embodiments, the alkali in the solution has a concentration of at least 10 wt%. The application may be by brushing, spraying, rolling, printing, or any other controlled surface application technique. In some embodiments, the first volume may be much smaller than the corresponding volume of the liquid oxidant applied in the subsequent processing block 122. For example, the first volume may be less than or equal to 20% of the volume of the liquid oxidant. In some embodiments, the first volume is in the range of 1 to 3 ml (including endpoints). By including a small amount of alkali, the decomposition of the liquid oxidant (e.g., H2O2) may be accelerated without causing a large amount of lignin removal from the wood. However, in some embodiments, the application of the alkali to the continuous piece of wood may be omitted.

[0095] Subroutine 104b may proceed to process block 122 where a second volume of liquid oxidant is applied to an upper exposed surface portion of the continuum corresponding to the first portion. For example, the liquid oxidant may be H2O2 at a concentration of at least 30 wt%. In some embodiments, the liquid oxidant may be applied to a surface portion of the first portion without additionally being applied to a surface portion of the second portion, thereby defining a pattern by the application of the oxidant. The application may be by brushing, spraying, rolling, printing, or any other controlled surface application technique. In some embodiments, a portion of the second volume may be applied to the upper exposed surface portion, while the remainder of the second volume may be applied simultaneously or subsequently to a lower exposed surface portion on the opposite side of the continuum.

[0096] In some embodiments, the second volume can be based on the surface area and / or thickness of the wood part to which the liquid oxidant is to be applied. For example, when the continuous piece has a thickness of about 0.6 mm (e.g., in a direction perpendicular to the upper exposed surface), the second volume of the applied liquid oxidant can be at least 800 ml / square meter of surface area. When the continuous piece has a thickness of about 0.8 mm, the second volume of the applied liquid oxidant can be at least 1200 ml / per square meter of surface area. When the continuous piece has a thickness of about 1 mm, the second volume of the applied liquid oxidant can be at least 2400 ml / square meter of surface area. Alternatively, the second volume of the applied liquid oxidant can be at least 125 ml per 0.1 mm thickness and per square meter of surface area. In some embodiments, the second volume of the applied liquid oxidant can be based on the volume of the wood part to which the liquid oxidant is to be applied. For example, the second volume can be at least equal to the volume of the wood part, or in the range of 1 to 5 times (including the end value) of the volume of the wood part. For example, the second volume can be 10 to 20 ml, including the end value.

[0097] Subroutine 104b may proceed to processing block 124, in which the continuous block is subjected to UV radiation from a natural light source (e.g., irradiation at a UV index of 5 or higher) or an artificial light source (e.g., 20W in the UVA band). In some embodiments, the entire upper surface may be exposed to UV radiation for a time sufficient to in situ modify the lignin in the first portion by photocatalytic oxidation, in particular to remove chromophores from the lignin. The exposure of processing block 124 may continue through decision block 126 until the photocatalytic oxidation reaction in the first portion has proceeded to completion, as evidenced by the first portion becoming completely white. In some embodiments, the exposure time may be less than or equal to 2 hours, such as 1 to 2 hours.

[0098] After exposure, the continuous block can retain at least 80% of the original lignin in the first portion that was previously white before processing (e.g., the lignin content is reduced by no more than 20%). In addition, since the adjacent second portion is not subjected to photocatalytic oxidation (e.g., because no oxidant is applied thereto), substantially all of the lignin originally therein should be retained. Therefore, the second portion can have a higher lignin content than the first portion, although only slightly. For example, after processing in processing block 124, both the first portion and the second portion can have a lignin content greater than or equal to 15 wt%.

[0099] Although some of the blocks 118-126 of the subroutine 104b have been described as being performed once, in some embodiments, multiple repetitions of a particular processing block may be employed before proceeding to the next decision block or processing block. For example, the application of the liquid oxidant in processing block 122 may be accomplished by multiple fractional applications (e.g., by brushing the same surface area multiple times (e.g., 3 to greater than 10 times) to cumulatively apply the desired second volume). Furthermore, although the blocks 118-126 of the subroutine 104b have been shown and described separately, in some embodiments, the processing blocks may be combined and performed together (simultaneously or sequentially). For example, applying a first volume of base in a solution in processing block 120 may be combined with applying a second volume of liquid oxidant in processing block 122. Furthermore, although Figure 1C The specific order of blocks 118-126 is shown, but the embodiments of the disclosed subject matter are not limited thereto. In fact, in some embodiments, the blocks may occur in a different order than shown, or may occur simultaneously with other blocks.

[0100] Figure 1D Shown can be used Figure 1A A third exemplary subroutine 104c of a chemical-based treatment of processing box 104 of method 100 is provided. For example, subroutine 104c can be used to form a continuous piece of patterned in-situ lignin modified wood or a patterned transparent wood composite. Subroutine 104c can begin with optional processing box 128, where a first volume of a base in a solution is applied to some or all of the upper exposed surface of the continuous piece. In addition, the details of processing box 128 can be similar to processing box 120 described above for subroutine 104b. Subroutine 104c can proceed to processing box 130, where a second volume of a liquid oxidant (e.g., H2O2) is applied to some or all of the upper exposed surface of the continuous piece. In addition, the details of processing box 130 can be similar to processing box 122 described above for subroutine 104c. Alternatively, in some embodiments, the application of processing box 130 can be performed by immersing the continuous piece of wood in a bath of the oxidant rather than surface applying the oxidant. After sufficient penetration of the oxidant and prior to UV exposure in processing block 132, the continuous wood piece may be removed from the bath.

[0101] Subroutine 104c may proceed to processing block 132, in which UV radiation from a natural or artificial light source is applied to the continuous piece. In some embodiments, UV radiation may be applied to the upper exposed surface portion of the first portion without additionally applying to the upper exposed surface portion of the second portion, thereby defining a pattern by UV exposure. For example, UV radiation from the light source may be passed through a photomask to shield exposure of the second portion. Alternatively or in addition, the UV light source may be a UV laser or laser diode (e.g., a Nd:YAG laser) that is constructed and controlled to sequentially irradiate only the upper exposed surface portion corresponding to the first portion. In some embodiments, UV exposure of the upper surface portion of the first portion may continue for a time sufficient to modify lignin in situ in the first portion by photocatalytic oxidation, particularly to remove chromophores from lignin. Exposure of processing block 132 may continue through decision block 134 until the photocatalytic oxidation reaction in the first portion has proceeded to completion, as evidenced by the first portion becoming completely white. In some embodiments, the exposure time may be less than or equal to 2 hours, such as 1 to 2 hours.

[0102] After exposure, the continuous block can retain at least 70% of the initial lignin in the existing white first portion before processing (e.g., the lignin content is reduced by no more than 30%). In addition, since the adjacent second portion is not subjected to photocatalytic oxidation (e.g., due to the lack of UV radiation thereon), substantially all of the lignin originally therein should be retained. Therefore, the second portion can have a higher lignin content than the first portion, although only slightly. For example, after processing at processing block 132, both the first portion and the second portion can have a lignin content greater than or equal to 15 wt%.

[0103] Although some of the blocks 128-134 of the subroutine 104c are described as being performed once, in some embodiments, multiple repetitions of a particular processing block may be employed before proceeding to the next decision block or processing block. For example, the application of the liquid oxidant in processing block 130 may be accomplished by multiple fractional applications (e.g., by brushing the same surface area multiple times (e.g., 3 to greater than 10 times) to cumulatively apply the desired second volume). In addition, although the blocks 128-134 of the subroutine 104c have been shown and described separately, in some embodiments, the processing blocks may be combined and performed together (simultaneously or sequentially). For example, applying a first volume of base in the solution in processing block 128 may be combined with applying a second volume of liquid oxidant in processing block 130. In addition, although Figure 1D The specific order of blocks 128-132 is shown, but the embodiments of the disclosed subject matter are not limited thereto. In fact, in some embodiments, the blocks may occur in a different order than shown, or may occur simultaneously with other blocks.

[0104] Natural patterned transparent wood composite material embodiment

[0105] The cell wall in natural wood is mainly composed of cellulose (40wt% to 50wt%), hemicellulose (20wt% to 30wt%) and lignin (20wt% to 30wt% for hardwood and 25wt% to 35wt% for softwood), and these three components are interwoven to form a strong and rigid wall structure. Natural hardwood has a unique three-dimensional porous structure with multiple channels or lumens formed by longitudinal units, including conduits 214 extending along the growth direction 210 of the wood (e.g., having a maximum cross-sectional dimension or diameter of 40-80μm (including end values) in a plane perpendicular to its length) and fibers 216 (e.g., having a maximum cross-sectional dimension or diameter of 10-30μm (including end values) in a plane perpendicular to its length), such as Figure 2B 212 in the exemplary section. Compared to hardwood, softwood relies on medullary rays and tracheids 215 extending along the wood growth direction 210 to transport water. Tracheids can have a maximum cross-sectional dimension or diameter that can vary depending on the location of the tracheid in the wood cross section.

[0106] Softwood is wood from gymnosperm trees such as pine (e.g., Eastern white pine, Lodgepole pine, Parana pine, Scots pine, Southern yellow pine, etc.), cedar (e.g., Red cedar, etc.), spruce (e.g., European spruce, Sitka spruce, etc.), larch, and fir (e.g., Douglas fir). Natural softwood exhibits an intrinsic aesthetic pattern of growth rings with alternating structures on both macro and micro scales. From a macroscopic perspective, the growth rings are the result of alternating formations of spring EW 218 and summer LW 220, such as Figure 2C-2D Each EW region 218 is generally wider, weaker, more porous, and lighter in color than each LW region 220. With regard to microstructure, the cells in the EW region 218 have a relatively larger diameter of the lumen 215a and a thinner cell wall than the lumen 215b in the LW region 220, as shown in FIG. Figure 2E shown.

[0107] The natural wood piece can be cut in any direction with respect to its longitudinal growth direction 210. Since the tracheids are naturally aligned with the growth direction, the cutting direction will determine the orientation of the hollow cells in the final structure, which can affect the optical or mechanical properties of the final transparent wood composite. For example, in some embodiments, the natural wood piece can be cut from the trunk 202 of the tree 200 along a vertical or longitudinal direction (e.g., parallel to the longitudinal wood growth direction 210) so that the longitudinal hollow cells are oriented substantially parallel to the major face of the longitudinally cut wood piece 206 (e.g., having the largest surface area). Alternatively, in some embodiments, the natural wood piece can be cut along a horizontal or radial direction (e.g., perpendicular to the longitudinal wood growth direction 210, also referred to as a transverse cut) so that the longitudinal hollow cells are oriented substantially perpendicular to the major face of the radially cut wood piece 204. Alternatively, in some embodiments, the natural wood piece can be cut along a rotational direction (e.g., perpendicular to the longitudinal wood growth direction 210 and along the circumferential direction of the trunk 202) so that the longitudinal hollow cells are oriented substantially parallel to the major face of the rotationally cut wood piece 208. In some embodiments, the natural wood piece may be cut in any other direction between longitudinal, radial and rotary cuts. For any cutting direction, the thickness of the natural wood piece may be measured perpendicular to the main face and may be 10 mm or less.

[0108] use Figure 2C-2E The natural pattern of alternating EW 218 and LW 220 regions shown in the Figure 2 can form a transparent wood composite that inherits the natural pattern and also has good optical and mechanical properties. For example, softwood can be subjected to spatially selective delignification and subsequent polymer infiltration, for example, as described above with respect to Figure 1A-1B As described. After spatially selective delignification, the EW region 218 becomes almost completely white due to the removal of light scattering and light absorbers (e.g., lignin and lignin extracts), while the LW region 220 retains some lignin. Subsequent infiltration with a refractive index matching polymer results in a continuous piece 304, whose adjacent portions have different optical properties, in particular, a portion 318 based on the substantially transparent original EW region 218 (e.g., at least 80% transmittance for light with a wavelength of 600 nm) and a portion 320 based on the substantially translucent or opaque original LW region 220 (e.g., less than 70% transmittance for light with a wavelength of 600 nm), as shown in FIG. Figures 3A-3C In addition, due to the different optical transmittance values ​​(based on delignification of EW region 218 relative to only partial removal of lignin in LW region 220), the retention of lignin in LW region 220 can endow the natural patterned transparent wood composite with enhanced mechanical strength and good UV absorption characteristics.

[0109] In some embodiments, a batch manufacturing process can be used to manufacture natural patterned transparent wood composites. For example, Figure 4A An exemplary manufacturing facility 400 employing batch operation is shown. In a first stage 402, a continuous piece 408 of softwood having well-defined EW 410 and LW 412 portions can be immersed in a delignified solution 406 (e.g., NaClO2) in a fluid chamber 404 for a predetermined period of time or until the EW portion 410 turns white. The resulting modified continuous piece 420 includes substantially delignified EW portions 422 alternating with LW portions 424 retaining non-white lignin. In a subsequent second stage 414, the modified continuous piece 420 is immersed in a liquid polymer or polymer precursor 418 in a chamber 416 (e.g., a vacuum chamber) so as to infiltrate the cellulose-based microstructure of the modified EW 422 portions and the LW 424 portions, thereby forming a transparent wood composite material 432 having fully transparent portions 434 alternating with translucent or opaque portions 436.

[0110] In some embodiments, the continuous piece is removed from the fluid chamber 404 of the first stage 402 and inserted into the chamber 416 of the second stage 414. Alternatively, in some embodiments, the fluid chamber 404 and the chamber 416 are identical, and the transition from the first stage 402 to the second stage 414 is achieved by replacing the delignification solution 406 with a liquid polymer or precursor 418. Although not specifically discussed above, it should be understood that the batch manufacturing facility 400 can also include one or more rinse stages (not shown).

[0111] In some embodiments, the batch manufacturing facility can optionally include a drying or polymerization stage 426 that employs a pressing facility (e.g., a hydraulic press). For example, the pressing facility can have a top platen 430 and a bottom platen 428, wherein one or both of the platens can be moved toward the other to apply pressure to the wood composite material 432 sandwiched therebetween. For example, the pressing facility can apply a nominal pressure to maintain the thickness and / or flatness of the upper and lower surfaces of the composite material 432 as the polymer therein hardens. In some embodiments, the pressing stage 426 can include heating the composite material 432 while pressing the composite material 432, such as by heating one or both of the platens 428, 430.

[0112] In some embodiments, a semi-continuous manufacturing process can be used to manufacture natural patterned transparent wood composites. For example, Figure 4B An exemplary manufacturing facility 450 is shown that employs a semi-continuous operation. Natural cork 452 may be in the form of logs or cylindrical sticks, wherein the lumen extends along direction 454. Natural wood 452 may be repeatedly cut with longitudinal blades 456, e.g. Figure 4CThe quarter-cut method is used to produce a long slice 458 having both an EW 482 region and an LW 484 region. The slice layer 458 can be conveyed to a delignification station 460 for the next step in the manufacturing process, for example, immersing the wood 458 in a chemical solution 462, for example, as described above with respect to processing box 112 of subroutine 104a, to delignify the EW portion but only partially remove lignin from the LW portion. In some embodiments, the size of station 460 and the conveyance speed of the wood layer 458 through station 460 can correspond to the desired immersion time for the chemical treatment. Therefore, the time from when a portion of the layer 458 enters station 460 to when it goes to rinse station 464 will correspond to the immersion time for removing the desired amount of lignin from the EW portion.

[0113] After the delignification station 460, the modified chip layer 458 may continue to be transported to the next sequential station, such as a rinse station 464. The rinse station may contain one or more solvents 466 (e.g., water, alcohol, etc.), and optionally one or more agitators designed to remove any residues of the delignification chemicals 462 within the modified layer. Figure 4B Only a single rinse station is shown, but multiple stations may be provided, for example, to allow solvent exchange prior to polymer infiltration.

[0114] After the rinsing station 464, the modified sliced ​​layer 458 can continue to be transported to the next sequential station, for example, a polymer station 468, which includes a liquid polymer or polymer precursor 472 in a chamber (e.g., a vacuum chamber). The cellulose-based microstructure that permeates the modified EW portion and the LW portion forms a transparent wood composite material 480, which has completely transparent portions alternating with semi-transparent or opaque portions.

[0115] In some embodiments, the manufacturing facility 450 may optionally include a drying or polymerization station 474 that employs complementary rollers 476, 478. In some embodiments, the upper roller 476 and the lower roller 478 are maintained at a fixed distance from each other that is substantially equal to or slightly less than the thickness of the composite wood 480, thereby applying a nominal pressure that prevents warping during drying or polymerization. In some embodiments, one or both of the rollers 476, 478 may be heated to raise the temperature of the composite material 480 above room temperature, for example, to promote polymer curing or polymerization. Alternatively or in addition, the rollers 476, 478 may not be heated, but a separate heating mechanism may be provided, or the environment containing the station 474 or after the station 474 may be heated.

[0116] In situ lignin modification example

[0117] In situ modification of lignin in hardwood or softwood is accomplished by a photocatalytic oxidation mechanism resulting from simultaneous exposure 501 of a native lignin form 503 to both an oxidant 505 (e.g., hydrogen peroxide) and UV radiation 507, such as Figure 5A As shown. Without being bound by any particular theory, UV light 507 acts as a photocatalyst, which promotes the formation of chromophores (Lig·) from lignin by cleaving conjugated double bonds and accelerating the decomposition of H2O2 into oxygen / peroxy radicals (O· / HOO·). The photoexcited Lig· and O· / HOO· then participate in a photocatalytic oxidation reaction to form non-conjugated carboxyl groups 509, resulting in the decolorization of the material and the formation of modified wood. In addition, a small reaction may occur in which a very small amount of aromatic ring structures in the lignin undergo a ring-opening reaction to form small molecules that are soluble in H2O2, which may contribute to a slight reduction in the lignin content of the wood after treatment (e.g., a reduction of no more than 20%). Since the reaction requires both UV light 507 and the oxidant 505, patterning of the wood can be achieved by applying both to the portions that need to be modified and applying UV or the oxidant (but not both) to the portions that do not need to be modified. In some embodiments, the in situ lignin-modified wood is used alone without further processing. Alternatively, in some embodiments, the modified wood is further processed by infiltration with a polymer to form a transparent wood composite.

[0118] In some embodiments, a batch manufacturing process can be used to manufacture the patterned transparent wood composite material. For example, Figure 5B An exemplary batch manufacturing operation is shown. In the initial stage 500, a continuous piece 502 of wood of any cut (e.g., R-cut, L-cut, T-cut, etc.) and any wood type (e.g., softwood or hardwood) is provided. The continuous piece 502 may have an upper surface 504, to which an oxidant is applied in a second stage 506. In some embodiments, a predetermined pattern profile 508 is first formed on the upper surface 504 to depict the first portion 510 for the second portion 512. For example, the pattern profile 508 may be formed using a hydrophobic material such as vaseline. Alternatively, in some embodiments, a physical profile 508 is not provided. Instead, physically applying an oxidant (and optionally a base before or simultaneously with the oxidant) to a specific portion of the upper surface 504 may define a predetermined pattern 508. For example, a controlled volume of an oxidant may be applied, coated, printed, or otherwise applied to the first portion 510 using a brush 514 without additionally applying the oxidant to the second portion 512. Other mechanisms for applying a controlled volume to a surface are possible in accordance with one or more contemplated embodiments.

[0119] In the third stage 516, the entire upper surface 504 can be exposed to UV radiation 518 from a natural or artificial light source. Alternatively, in some embodiments, only the first portion 510 can be exposed to UV radiation 518 (e.g., in a manner similar to Figure 5C In either case, the combination of the oxidant and UV radiation in the first portion but not in the second portion 512 causes photocatalytic oxidation to occur only in the first portion 510. The modified wood 522 (e.g., photo-stimulated wood) obtained in stage 520 has a first portion 524 and a second portion 526, wherein the first portion 524 is in-situ lignin-modified and thus is substantially white in color, and the second portion 526 retains its natural lignin and thus is substantially non-white in color (e.g., natural wood color). In some embodiments, the modified wood 522 of stage 520 can be used as is, for example, as an insulating or optically reflective material.

[0120] Alternatively, in some embodiments, the modified wood 522 is further processed at a final stage 528, for example, by infiltrating the wood 522 with a refractive index matching polymer to form a patterned transparent wood composite 530 having a transparent first portion 532 and an adjacent translucent or opaque second portion 534. For example, by immersing the polymer in a liquid polymer or polymer precursor and applying a vacuum for a period of time, the polymer can penetrate into the microstructure of the modified wood 522, for example, as described above with respect to Figure 1A discussed.

[0121] Figure 5C Another exemplary batch operation for making a patterned transparent wood composite material is shown. In a second stage 536, an oxidant 538 may be applied to the entire upper surface 504 of the continuous piece of wood 502. In some embodiments, a brush or other mechanism may be used to apply a controlled volume of the oxidant to the entire upper surface 504, for example, in a manner similar to that described above with respect to Figure 5B 506. Alternatively, the application of the oxidant may be accomplished by immersing the surface 504 or the entire continuum 502 in an oxidant bath. In a third stage 540, only a portion of the upper surface 504 corresponding to the predetermined pattern is exposed to UV radiation. For example, a uniform UV radiation field 542 may be incident on a photomask 544 having open or transparent areas 546 that allow light to pass through to expose the upper surface of the first portion 548, while otherwise blocking the upper surface of the second portion 550 from exposure to light.

[0122] The combination of the oxidant and UV radiation in the first portion 548 but not in the second portion 550 results in photocatalytic oxidation occurring only in the first portion 548. The modified wood 553 (e.g., photo-stimulated wood) obtained in stage 552 has a first portion 554 and a second portion 556, wherein the first portion 554 is in-situ lignin modified and thus is substantially white in color, and the second portion 556 retains its natural lignin and thus is substantially non-white in color (e.g., natural wood color). In some embodiments, the modified wood 553 of stage 552 can be used as is, for example, as an insulating or optically reflective material.

[0123] Alternatively, in some embodiments, the modified wood 553 is further processed at a final stage 558, for example, by infiltrating the wood 553 with a refractive index matching polymer to form a patterned transparent wood composite 560 having a transparent first portion 562 and an adjacent translucent or opaque second portion 564. For example, by immersing the polymer in a liquid polymer or polymer precursor and applying a vacuum for a period of time, the polymer can be infiltrated into the microstructure of the modified wood 553, for example, as described above with respect to Figure 1A discussed.

[0124] Figure 5D An exemplary batch operation for making a transparent wood composite material is shown. In a second stage 566, an oxidant may be applied to the entire upper surface 504 of the continuous wood piece 502, for example, in a manner similar to Figure 5C The second stage 536 of the embodiment of the present invention and / or the use of a brush 514 or other mechanism to control the volume of the oxidant applied, for example, in the same manner as described above with respect to Figure 5B In a similar manner as described in the second stage 506 of . Alternatively, the application of the oxidant can be achieved by immersing the surface 504 or the entire continuous piece 502 in an oxidant bath. In the third stage 568, the entire upper surface 504 can be exposed to UV radiation 518 from a natural or artificial light source. The combination of the oxidant and UV radiation in the entire continuous piece 502 causes photocatalytic oxidation to occur anywhere (e.g., without any patterning). The modified wood 572 (e.g., photoexcited wood) obtained in stage 570 has all in-situ lignin modified, so the color is basically white. In some embodiments, the modified wood 572 of stage 570 can be used as it is, for example, as an insulating or optically reflective material. Alternatively, in some embodiments, the modified wood 572 is further processed in the final stage 574, for example, the wood 572 is infiltrated with a refractive index matching polymer to form a transparent wood composite material 576. For example, by immersing the polymer in a liquid polymer or polymer precursor and applying a vacuum for a period of time, the polymer can penetrate into the microstructure of the modified wood 572, for example, as described above with respect to Figure 1A discussed.

[0125] In some embodiments, a semi-continuous or continuous manufacturing process may be used to manufacture a transparent wood composite material (whether patterned or unpatterned). Figure 6 An exemplary manufacturing facility 600 employing continuous operation is shown. Natural wood 602 may be in the form of a log or cylindrical bar in which the lumen extends in a direction perpendicular to the page. Natural wood 602 may be continuously cut by a rotary lathe 604, for example, to separate thin continuous layers 606 of natural wood for subsequent processing. Natural wood layer 606 may be transported to station 608 for the next step in the manufacturing process, for example, applying a controlled amount of liquid oxidant 612 to the surface using a brush 610 or other mechanism.

[0126] After station 608, the wood layer 606 can be transported to the next sequential station, such as a UV exposure station 614. The UV exposure station 614 can include an artificial light source 616 and one or more optical elements 620 (e.g., reflectors) designed to irradiate the wood with a substantially uniform light beam 618. Alternatively, in some embodiments, the UV exposure station 614 utilizes natural sunlight instead of using an artificial light source. As in the above-described embodiment, the combination of UV exposure and an oxidant in the wood leads to photocatalytic oxidation, which modifies the lignin in the wood in situ, particularly by removing its chromophore without significantly reducing the lignin content. In some embodiments, the size of the station 614 and the speed at which the wood layer 606 is transported through the station 614 can correspond to the desired UV exposure time (e.g., 1 to 2 hours). Therefore, the time from a portion of the layer 606 entering the station 614 to the time of going to the polymer penetration station 624 will correspond to the exposure time of the in situ lignin modification.

[0127] In some embodiments, the modified wood 622 produced by station 614 can be used without further processing. Alternatively, in some embodiments, the modified wood 622 is further transported to the next sequential station, such as a polymer station 624, which includes a liquid polymer or polymer precursor 626 in a chamber 628 (e.g., a vacuum chamber). The cellulose-based microstructure that penetrates into the modified wood 622 forms a transparent wood composite material 630.

[0128] Manufacturing Examples and Experimental Results

[0129] Example 1 - Natural patterned transparent wood composite material

[0130] A natural patterned transparent wood composite (also called aesthetic wood) is manufactured based on two different wood cuts, specifically a radial (R) cut in which the aligned channels of the cellulose-based microstructure extend in a direction perpendicular to the main surface (e.g., the surface exposed to incident light to be transmitted) and a longitudinal (L) cut in which the aligned channels of the cellulose-based microstructure extend in a direction parallel to the main surface. Douglas fir was chosen because of the clear contrast in both color and density between the earlywood (EW) and latewood (LW) parts. Fig. 7A As shown in FIG. 1 , the cellulose-based microstructure of Douglas fir shows a distinct boundary between the EW portion and the LW portion. Compared to the sidewalls (e.g., having a thickness of about 15.7 μm) and the lumen in the LW portion, the cellulose-based microstructure of Douglas fir in the EW portion (e.g., having a thickness of about 15.7 μm) Figure 7A-7B The microstructure has thin sidewalls (e.g., a thickness of about 3.8 μm in a plane substantially parallel to the radial direction of the wood) and larger lumens (e.g., a cross-sectional dimension in a plane substantially parallel to the radial direction of the wood) (e.g., Fig. 7A and 7C Wood tracheids (e.g. Fig.7D The distribution of hollow tubular structures (as shown in ) varies depending on the specific wood fraction, with the EW fraction having a lumen diameter range of approximately 20-80 μm (see Fig. 7E ), the LW portion has a lumen diameter range of approximately 5-35 μm (see Figure 7F ). Therefore, different pore size distributions can indicate different densities of EW and LW.

[0131] The effect of delignification was analyzed using R-cut pieces of Douglas fir continuous blocks measuring 60 mm × 60 mm × 2 mm. Colored components (mainly lignin, as well as extractives) were removed from bulkwood using an acidic NaClO2 solution (80%). The solution was prepared as follows: NaClO2 powder was dissolved in deionized (DI) water, and then acetic acid was added to adjust the pH (about 4.6). Each wood sample was placed in a boiling NaClO2 solution for a period of time (e.g., 2 hours) until the EW portion turned white. The delignified wood samples were then rinsed at least three times with DI water and then stored in ethanol until further processing. To form a natural patterned wood composite, an epoxy resin (e.g., AeroMarine 300 / 21 epoxy resin, a transparent, low viscosity cycloaliphatic epoxy resin system, AeroMarine Products, Inc., San Diego, CA) was infiltrated into the processed wood sample. The epoxy resin was cured for about 24 hours to obtain a natural patterned wood composite.

[0132] Differential (e.g., spatially selective) delignification between the EW portion and the LW portion (e.g., based at least in part on the density difference between EW and LW) can be achieved by boiling immersion in a NaClO2 solution for as little as 2 hours. After 2 hours of treatment, the EW portion is almost completely white, while the LW portion retains its color due to residual lignin and other colored components. The main reason for spatially selective delignification is the inherent structural difference between the EW portion and the LW portion, which correspondingly causes the solution in the EW portion to diffuse faster than in the adjacent LW portion. After immersion in a boiling NaClO2 solution for 2 hours, the weight of each wood sample was reduced by about 13.5%. However, the nanoscale and macroscale features of natural wood (e.g., cellulose-based microstructure) are substantially retained. In order to convert the LW portion into a completely white color, a longer treatment time (e.g., about 10 hours) is required, with a corresponding increase in weight loss (e.g., a weight reduction of about 35%). Due to these longer processing times, the structural integrity of delignified wood may not be well maintained, resulting in poor mechanical properties, partly due to the EW fraction (e.g., about 284.6 kg·m -3 ) and LW part (e.g., about 846 kg·m -3 ) and the lack of lignin in both the EW and LW fractions.

[0133] To evaluate the distribution of lignin in softwood scaffolds after spatially selective delignification, Raman spectroscopy imaging was used in combination with vertex composition analysis (VCA). Figure 7G Raman spectra obtained for both the EW and LW fractions of native wood and spatially selectively delignified wood are shown. In particular, Figure 7G The characteristic bands of lignin components are shown at 1598 cm -1 、1656cm -1 and 1269cm -1 (the marker bands of aryl-OH and aryl-OCH3 in the guaiacyl (G) unit in lignin), respectively, are attributed to the CH band of aromatic C=C stretching, coniferyl alcohol C=C, C=O stretching and C=C, and aromatic C=C stretching. Compared with the EW and LW parts in natural wood, the representative lignin band in the cell wall in the EW part of the spatially selectively delignified wood almost disappeared, while the representative lignin band in the cell wall in the LW part of the spatially selectively delignified wood remained. At the same time, after NaClO2 treatment, the corresponding cellulose peaks (e.g., 1095 cm -1 These results suggest that in spatially selective delignified wood, most of the lignin in the EW fraction has been removed, while a small portion of the lignin in the LW fraction remains, leading to the formation of a natural pattern in the continuous wood block.

[0134] Follow the same procedure as above to create a continuous block of L-cut pieces of Douglas fir using a straight pattern instead of a loop pattern (using Figure 4C quarter-slice cutting). The efficient spatially selective delignification process not only imparts excellent structural integrity but also facilitates large-scale production of L-cut natural patterned transparent wood composites. For example, a continuous block of L-cut natural patterned transparent wood composite with a size of 320 mm × 170 mm × 0.6 mm was produced, which is significantly larger than traditional attempts to make transparent wood using delignified wood as a frame. The L-cut natural patterned transparent wood composite is optically transparent with a total transmittance of 87% (e.g., from both the EW part and the LW part) and an optical haze of 65% at 600 nm.

[0135] The L-cut natural patterned transparent wood composites exhibited a large number of arranged dense microchannels along the wood growth direction after successful infiltration. In the cross-sectional view, although the lumens in the LW section are much smaller than those in the EW section, the lumens are dense. In addition, the channels and pores in each section are completely filled with polymers (e.g., epoxy resin), which act as adhesives, producing strong interactions between the cellulose cell wall and the polymer itself. Raman spectroscopy imaging was further performed to identify the distribution of the impregnated polymer in the resulting wood cells, including cell corners (CC), composite middle layers (CML), cell walls (CW), and lumens. According to Figure 7H The corresponding Raman spectra in the tube show that the strong signal peaks in the lumen indicate the bond stretching of the epoxy resin, especially at 640 cm -1 (aromatic CH out-of-plane deformation), 1001cm -1 (polyamidoamine adduct, amino) and 1608 cm -1 (Aromatic ring breathing mode). The polymer signals can also be detected in CML / CC and CW, indicating that the polymer has penetrated well into the wood cells and formed a strong interface with the cellulose in the delignified wood scaffold.

[0136] The hierarchical cellular structure of spatially delignified wood results in unique anisotropic mechanical characteristics. For example, compared with natural R-cut wood (e.g., 6.24 MPa), the natural patterned transparent wood composite formed from R-cut wood exhibited significantly improved tensile strength (e.g., 21.56 MPa), and the natural patterned transparent wood composite formed from L-cut wood exhibited even higher tensile strength (e.g., 91.95 MPa). The toughness of the natural patterned transparent wood composites made from R-cut wood and L-cut wood was 0.523 MJ m -3 and 2.73MJ m -3 .

[0137] In addition, the uneven distribution of lignin and cell structure between the EW and LW parts in natural patterned transparent wood composites can lead to uneven light transmittance. Fig.7I As shown, eight positions within the EW (1-8) and LW (1'-8') sections of the natural patterned transparent wood composite material formed by R-cut wood were selected, and the transmittance at 600 nm was measured. The LW section showed a lower transmittance (e.g., an average of about 68%) than the EW section (e.g., an average of about 86%). Although the transmittance value in the LW section is lower, the LW section only slightly reduces the overall average transmittance of the natural patterned transparent wood composite material for light in the visible light spectrum (e.g., at least wavelengths between 600 and 700 nm, including the end values).

[0138] In addition, the retention of lignin in the LW portion gives the natural patterned transparent wood composite a unique UV blocking ability (e.g., for wavelengths in the range of 200 to 400 nm, inclusive), which can be adjusted according to the time of the delignification treatment. For example, when a continuous wood block with a thickness of 2 mm is subjected to a delignification treatment time of 2 hours, the subsequent transparent wood composite is able to shield almost 100% of the UVC (200-275 nm) and UVB (275-320 nm) spectra and most of the UVA (320-400 nm) spectrum. However, if the delignification treatment time is extended to, for example, 9 hours, the UVA shielding ability of the resulting transparent wood composite is significantly reduced, as shown in FIG. Figure 7K As shown. The excellent UV blocking performance is attributed to the presence of phenylpropane structures and phenolic hydroxyl groups in the lignin molecules with UV absorption ability. Therefore, the natural patterned transparent wood composites formed by continuous wood blocks subjected to 2 hours of delignification treatment present a unique combination of features, especially good UV absorption in the range of 200-400 nm (e.g., ≥80%), high average transparency at 600 nm (e.g., ≥80%), and low reflectivity for visible light wavelengths (e.g., ≤20%).

[0139] The natural patterned transparent wood composites also showed anti-glare and light-guiding capabilities. For example, the natural patterned transparent wood composites largely forward-scattered light, resulting in a high optical haze of about 93%, as shown in Figure 2. Figure 7L As shown. Since the transparent wood composite inherits the aligned microstructure of natural wood, light can propagate along the microchannels once the wood cavity is filled with a refractive index matching polymer (e.g., epoxy resin). The microchannels act as lossy waveguides, providing the transparent wood composite with remarkable performance.

[0140] The pattern of the transparent wood composite is defined by the natural pattern of the EW and LW portions in a continuous piece of raw wood. However, other types of patterns can be achieved by stacking together multiple transparent wood composite layers 700, each of which can be from the same tree, from the same tree species (e.g., all are Douglas fir, but from different trees), or from different softwoods (e.g., one is fir and the other is pine). For example, Figure 7M As shown, the lattice pattern in assembly 704 can be formed by arranging two (or more) layers 700a, 700b in a stack 702, the layers having patterns that are rotated relative to each other. This capability has potential applications in patterned ceilings based on high light transmittance and inherent aesthetics.

[0141] At the same time, aesthetically pleasing wood can also improve energy efficiency due to its superior thermal insulation properties compared to glass. For example, the natural patterned transparent wood composite exhibited a radial (i.e., perpendicular to the longitudinal growth direction) thermal conductivity of 0.24 W·m - 1 K -1 The thermal conductivity is lower than that in the longitudinal growth direction (e.g., about 0.41 W·m -1 K -1 ), and is lower than the isotropic thermal conductivity of ordinary window glass (e.g., about 1 W·m -1 K -1 ). The anisotropic heat transport of transparent wood composites combined with this low thermal conductivity could be used to replace glass in energy-efficient buildings.

[0142] To demonstrate the use of natural patterned transparent wood composites as building materials with high transparency and high haze, model houses were built using glass and transparent wood composites as skylights. Using an external white light source directed toward the skylight, the light intensity at different points within each model house was detected and compared. In the model house with glass skylights, the maximum light intensity (e.g., 56.8 mW cm -2 ) than the minimum light intensity (e.g., 3.4 mW·cm -2 ) is about 17 times higher, which produces uneven lighting. In contrast, the model house with transparent wood composite skylights has a more uniform diffuse light distribution, with a maximum light intensity of 48.2mW·cm -2 , the minimum light intensity is 20.9mW·cm -2 .

[0143] The weathering stability of the natural patterned transparent wood composites was also evaluated by exposing the materials outdoors for 3 weeks and measuring the optical and mechanical properties. For the transparent wood composites formed from R-cut wood, the transmittance of the composites decreased slightly after exposure compared to before exposure, while the haze increased from about 93% to about 98% in the wavelength range of 400–800 nm. The transparent wood composites formed from L-cut wood experienced similar changes in transmittance and haze properties after exposure. Similar trends were observed in transmittance and haze in the aesthetic wood L. However, exposure did not affect the mechanical properties of any of the cut pieces of the transparent wood composites. In contrast, there was no significant decrease in the strength of the transparent wood composites due to exposure, indicating that the composites have at least short-term weathering capabilities.

[0144] In the above examples, softwood was used to take advantage of the spatially selective delignification of natural parts based on continuous wood pieces. Although both hardwood and softwood are suitable in principle, hardwood has a significantly different structure, consisting of vessels and fibers, while softwood is mainly composed of tracheids. For example, basswood is a hardwood with a substantially uniform cell wall thickness of about 5.8 μm, which is much thinner than the cell wall thickness of the LW part of Douglas fir. In addition, in terms of lumen diameter, the tracheal channels in basswood are larger than the relatively narrow tracheids of Douglas fir, and the tracheal channels present a bimodal pore size distribution. As a result, the reactions of the EW and LW parts of basswood are basically synchronized, so that almost no obvious wood pattern is retained after 2 hours of treatment. Similar results were obtained for fir wood (another hardwood with bimodal pores, so the solution diffusion is basically uniform). However, hardwood presents significant differences in density, porosity, cell wall thickness, lumen cross-sectional size, or any combination of the foregoing, and the results of different solution diffusion or reaction efficiency between different natural parts can be used to form natural patterned transparent wood composites according to the embodiments of the disclosed subject matter.

[0145] Example 2 - In situ lignin modification of wood

[0146] The natural lignin in a continuous block of wood is chemically modified in situ by UV-assisted photocatalytic oxidation to produce modified wood (also known as in-situ lignin-modified wood, lignin-modified wood, or photo-stimulated wood). During the UV-assisted photocatalytic oxidation process, the conjugated double bonds are cleaved to remove the chromophores of the lignin while retaining the bulk aromatic skeleton of the lignin, which continues to provide mechanical strength. Therefore, the modified wood retains most of the lignin in the original wood (e.g., ≥80%), and the removal of the chromophores gives the modified wood unique optical properties. In particular, the modified wood exhibits high optical whiteness (e.g., reflectivity ≥90% for light with a wavelength in the range of 400-800nm ​​(including end values), a complete cellulose-based microstructure, improved mechanical strength (e.g., about 20MPa wet tensile strength), significant water stability, and improved scalability (e.g., up to 2 meters) compared to existing delignification technologies for producing optical properties in wood.

[0147] In natural wood, vertically aligned wood channels enable efficient penetration of H2O2 and UV light into the wood structure to achieve rapid and deep decolorization, which can be achieved in less than 7 hours (e.g., 1 to 6.5 hours, depending on the thickness of the continuous piece of wood in a direction perpendicular to the surface of the wood piece where the UV light is incident). In addition, wood can be selectively decolorized by H2O2 printing in combination with UV light irradiation (e.g., using a cardboard engraving as a mold for applying H2O2 to the wood surface), which allows customized predetermined patterns of regions with different optical properties to be generated directly within a continuous piece of wood.

[0148] Balsa is used to prepare the modified wood because of its low density and hierarchical porous microstructure, but other hardwoods or softwoods can also be used. First, the balsa sample is impregnated with H2O2, specifically each continuous sample block is immersed in a 30% H2O2 solution, to which a 10% NaOH solution is added. A small amount of alkali can be used to accelerate the decomposition of H2O2 without causing the removal of a large amount of lignin from the balsa. Each H2O2-impregnated balsa sample is then exposed to UV radiation using an artificial light source (UVA band, 20W power) until the sample turns completely white. For example, natural balsa changes from brown to completely white after about 2 hours of UV radiation exposure (combined with H2O2 exposure). In contrast, when H2O2 is used without UV light, the color of the wood turns yellow. Note that lignin has many photolabile chromophore groups (e.g., quinone groups and conjugated double bonds) that easily absorb high-energy photons of UV light to generate chromophore free radicals. Therefore, the photoexcited chromophore radicals can react effectively with H2O2, resulting in photocatalytic oxidative degradation of the chromophore groups, eliminating the brown color of natural wood. At the same time, despite the fact that lignin is sensitive to UV radiation, the color of the wood did not change significantly when only UV light was applied. Moreover, if H2O2 treatment was used during any UV exposure, even 10 hours of exposure to H2O2 was not enough to modify natural balsa wood to have the white color obtainable using a combination of H2O2 and UV exposure. This suggests that the use of chemical oxidants alone may not be sufficient to completely bleach wood, or at least not on the same time scale as the combination of chemical oxidants and UV irradiation.

[0149] The combination of H2O2 and UV exposure further allows to modify the optical properties of wood without removing a significant amount of lignin therefrom, thereby enabling an enhancement of the mechanical strength of the modified wood compared to conventional delignification. The compositional content of the modified wood was measured using an acid hydrolysis method, and the acid insoluble lignin (Klason lignin) was determined gravimetrically. Fig. 8A It is shown that during the UV-assisted photocatalytic oxidation treatment, the normalized lignin content only slightly decreases with increasing treatment time. For example, after 2 hours of UV-assisted photocatalytic oxidation (enough to completely whiten the sample), the lignin content in the modified wood is 19.29 wt%, which is equivalent to about 82% of the initial lignin content in the natural balsa wood raw material (e.g., 23.5 wt%). In addition, as Figure 8B The Fourier transform infrared (FTIR) spectrum of the modified wood (photon) showed that the peaks at 1592, 1505 and 1430 cm -1 There is an absorption peak at , indicating that the aromatic skeleton lignin structure is well preserved.

[0150] The chemical structure of the modified wood was further analyzed using X-ray diffraction spectroscopy (XDS) and X-ray photoelectron spectroscopy (XPS). A Rigaku Ultima III equipped with a bending detector manufactured by Rigaku Americas Corp. (operating tube voltage 40 kV, tube current 30 mA, Cu Kα, ) collect X-ray diffraction (XRD) patterns. Figure 8C As shown, the XRD pattern of the cellulose crystal structure in the modified wood showed diffraction peaks at 16° and 22.6°, which represent the lattice type I structure of native cellulose (CrI), which confirms that the UV-assisted photocatalytic oxidation process does not change the crystal structure of the original wood. For the XPS experiment, the peak position was calibrated by the binding energy of C1s as a reference of 284.6 eV. Fig.8D The C1s spectra of natural wood and modified wood are shown. The XPS spectrum of the photoexcited wood has a high energy shift compared to the starting material. After UV-assisted photocatalytic oxidation treatment, the calculated oxygen-carbon (O / C) ratio changed from 0.26 to 0.42, indicating that the modified wood has a higher oxygen atomic percentage and a lower carbon atomic percentage, which may be due to the oxidation reaction on the lignin surface, resulting in an increase in the amount of OC=O and C=O groups. This in turn indicates that the conjugated double bonds (C=C) of the chromophore are opened to form non-conjugated carboxyl groups.

[0151] The above results, in addition to the color change of the modified wood to white, confirm that UV-assisted photocatalytic oxidation allows in-situ modification of lignin to change its chromophore while retaining most of the lignin skeleton. Unlike other non-in-situ lignin modification techniques, the disclosed technology allows in-situ modification of natural lignin, which is composed of a phenyl backbone and oxygen-containing branches, and is connected by a series of CO and CC bonds. This intact lignin structure helps to eliminate its chromophore while retaining as much of the lignin skeleton structure as possible during the photocatalytic oxidation process.

[0152] As described above, natural wood can have large duct channels with a diameter of hundreds of microns (~100-300 μm), as well as small fiber lumens with a diameter of tens of microns (about 20-50 μm) decorated by pits (about 0.8-10 μm) of different size ranges. These layered and interconnected microstructures serve as an effective pathway for the photocatalytic oxidation process, enhancing H2O2 penetration and UV light capture, which leads to an effective synergistic reaction to obtain modified wood. In addition, after the photocatalytic oxidation process, the wood scaffold structure with its hierarchical pores can be maintained. In particular, the cell wall thickness of the modified wood (about 2.06 μm) is similar to that of the natural balsa wood raw material (about 2.09 μm). For comparison, delignified wood is produced by immersing natural balsa wood in a boiling chemical solution (e.g., 5 wt% NaClO2 aqueous solution, acetic acid is added to adjust the pH to about 4.6) until the wood turns completely white. As Figure 8F As shown, the cell walls of this delignified wood were significantly thinned (about 1.46 μm) after treatment, and the underlying cellulose-based microstructure was substantially altered.

[0153] In order to explore the uniformity of the treatment on the thickness of the modified wood, a cross-section of a continuous block of modified wood (38mm×30mm×9mm) was taken along the longitudinal growth direction and divided into three parts (part "I" corresponds to the 3mm adjacent to the top surface of the block irradiated with UV light, part "III" corresponds to the 3mm adjacent to the bottom surface of the wood block opposite to the top surface, and part "II" corresponds to the 3mm between part I and part III). No obvious visual differences were observed between the three parts; instead, all wood showed the same level of whiteness, indicating that the wood was continuously decolorized by UV-assisted photocatalytic oxidation. The microstructure of the three parts was also similar, showing an intact wood microstructure. FTIR analysis showed that the three parts also had the same components, retaining the bulk structure of lignin. In addition, Fig. 8E The reflectance spectra shown in show that all three fractions exhibit high reflectance for visible light (about 90-96%). Without being bound by any particular theory, it is believed that the uniform properties of the modified wood are due to the rapid penetration of O· / HOO· and the efficient propagation of UV light deep into the wood, which may be caused by the channel structure of natural wood.

[0154] The disclosed photocatalytic oxidation technology presents many advantages compared to delignification methods. First, the use of H2O2 (a green oxidant that decomposes into water and oxygen without producing any toxic gases or liquids) is believed to be more environmentally friendly than delignification methods (e.g., the use of NaClO2 solutions, which can produce large amounts of toxic chlorine gas). Second, the processing time required for photocatalytic oxidation can be significantly less than delignification. For example, the disclosed photocatalytic oxidation can decolorize (convert the wood to white) a 5 mm thick block of wood in as little as 3.8 hours, while delignification may require at least 6 hours to achieve similar decolorization. Third, compared to delignification, the photocatalytic oxidation process also better retains the lignin content (82% vs. 1.4%) by selectively removing chromophores while retaining the bulk aromatic structure of the lignin. In fact, by retaining most of the lignin after processing, the modified wood can retain the original cellulose-based microstructure of the wood, such as Figure 8F In contrast, the cell walls of delignified wood have larger gaps and partial kinks, which detract from the structural morphology.

[0155] The lignin retained in the modified wood is used as a mechanical adhesive, which provides mechanical strength and prevents it from decomposing. The wood sample is kept in ultrapure water for 20 minutes, and then the sample is mechanically tested after removing excess water from the sample surface. The tensile properties of natural wood, modified wood and delignified wood samples are measured using a Tinius Olsen H5KT tester. The size of the tensile sample is about 50mm×5mm×1.5mm. The sample is stretched along the length direction of the sample until it breaks at a constant test speed of 5mm / min. Under these humid conditions, the tensile strength (along the longitudinal growth direction) shown by the modified wood is 20MPa, which is 20 times the tensile strength (1MPa) of the fully delignified wood, and is essentially the same as the unmodified natural wood. In this case, compared with delignified wood, the in-situ modified lignin of the modified wood can keep the cellulose fibers together to enhance the tensile properties of the wood.

[0156] The compression properties of phototreated and delignified wood samples were measured using a Tinius Olsen H5KT tester. The dimensions of the tensile samples were approximately 20 mm × 10 mm × 10 mm. The samples were compressed at a constant test speed of 5 mm / min in directions perpendicular and parallel to the tree growth direction. The modified wood exhibited higher compressive strength due to the support of rigid lignin, while the pressure applied to the delignified wood resulted in irreversible collapse of the cell wall. After releasing the pressure, the modified wood recovered without significant deformation (thickness change after compression Δh = 1.5 mm). In contrast, the delignified wood could not recover, resulting in high compression deformation (Δh = 8.4 mm). The compression test of the wood samples was also in good condition in the direction parallel to the tree growth direction. At the same compression displacement (1.6 mm), the delignified wood showed collapse of the cell wall, while the modified wood did not show structural damage or significant reduction in compressive strength.

[0157] Due to the hydrophobicity of the aromatic rings of lignin, in-situ modified lignin can also act as a barrier to water and improve the water stability of the modified wood. Water stability tests were conducted by placing natural wood, modified wood, and delignified wood blocks in water. The dimensions of the wood in this experiment were 4.5 cm × 4.5 cm × 0.45 cm. Natural wood, phototreated wood, and delignified wood were placed in water at the same time, and the thickness was recorded every minute. The delignified wood absorbed more water, resulting in a greater change in mass than the modified wood. In this case, without the shielding of hydrophobic lignin, the loose cellulose fibers of the hydrophilic delignified wood are more sensitive to water. At the same time, the high water absorption of delignified wood also leads to more obvious changes in the thickness of the material. The water absorption of the samples was also measured, in which one end of the wood was placed in a methylene blue (MB) solution. The delignified wood is characterized by the highest level of MB adsorption, followed by the modified wood, which again shows that water can more easily penetrate the delignified wood due to the lack of hydrophobic lignin.

[0158] After immersing the samples in water for three weeks to study their water stability, the delignified wood completely broke down into short fibers, while the modified wood maintained its shape without noticeable changes. Due to the lack of lignin, water was able to penetrate into the delignified wood and destroy the accessible and loose cellulose hydrogen bonds, resulting in its weaker mechanical properties. At the same time, due to the hydrophobicity and bonding effects of lignin, the microfibers of the phototreated wood are cross-linked, and water is unable to destroy the hydrogen bond structure of cellulose, which in addition to its improved mechanical characteristics, also achieves the excellent water stability of the phototreated wood.

[0159] While the manufacturing embodiments discussed above achieve modification of the entire continuous block, photocatalytic oxidation techniques can be used to form adjacent portions within the continuous block having different properties, for example, according to a predetermined two-dimensional or three-dimensional pattern that is independent of the natural pattern of the wood. In particular, since both UV light and a chemical oxidant (H2O2) are used to achieve decolorization within a specific treatment time, the controlled application of both to specific portions of the wood can determine the properties produced. For example, H2O2 can be printed (e.g., brushed, painted, sprayed, or otherwise applied to the surface without impregnating the entire continuous block) on the surface of natural wood in a specific pattern (e.g., using an engraved cardboard mold), and then the surface is irradiated with UV radiation. Portions of the wood that receive both UV and H2O2 will be modified, while portions of the wood that receive only one or neither will not be modified. For example, a pattern is printed on the surface of a continuous block of wood using 30% H2O2, and then the surface is exposed to UV light to form patterned modified wood. Figure 8G-8H Chinese knot patterns and star patterns are shown formed in various continuous wood blocks using this technique, where the lignin in portions 804, 808, 812 is modified in situ to remove chromophores therefrom, thereby appearing white, and the lignin in portions 802, 806, 810, 814 is substantially unmodified (e.g., the natural form of lignin). Alternatively, H2O2 can be applied to the surface of the entire wood block and natural wood and then irradiated with UV radiation in a specific pattern. Thus, through this simple, sustainable, large-scale, low-cost synergistic photocatalytic oxidation process, natural wood can be selectively decolorized on its surface by patterning on demand.

[0160] Example 3 - Transparent Wood Composite Material

[0161] The natural lignin in a continuous wood block is in situ chemically modified by UV-assisted photocatalytic oxidation to produce modified wood, which is then infiltrated with a refractive index matching polymer to form a transparent wood composite (also known as an in situ lignin modified transparent wood composite, an artificially patterned transparent wood composite, or a transparent wood). Balsa logs are cut in the transverse and longitudinal directions to form wood slices (thickness ranges from 0.6 mm to 3.5 mm, including end values). For each balsa slice, a trace amount of NaOH (2-3 ml, concentration of 10 wt%) is applied (e.g., brushed) on the top surface (perpendicular to the thickness direction) before brushing H2O2 to improve the oxidation efficiency of H2O2. Then, the top surface of each wood slice is brushed with H2O2 (≥15 ml, concentration of 30 wt%, volume depends on the thickness of the wood), and then the top surface is irradiated until the sample is completely whitened. A UV lamp with an emission wavelength of 380-395 nm is used for UV irradiation of the modified wood. For example, about 15 ml of H2O2 (at a concentration of 30 wt%) is brushed on a natural balsa wood sample measuring 200 mm × 10 mm × 0.6 mm and then exposed to UV light for 1 hour until the natural wood color completely turns white. This process removes chromophores in lignin, causing the wood color to change from brown to white. The treated wood pieces are then immersed in ethanol for 5 hours to remove any residual chemicals and then transferred to toluene to exchange the ethanol in the wood. Subsequently, each treated wood piece is impregnated with an epoxy resin (e.g., AeroMarine 300 / 21 epoxy resin, a clear, low viscosity cycloaliphatic epoxy resin system, AeroMarine Products, Inc., San Diego, CA) by vacuum infiltration for 1.5 hours. Finally, the wood samples impregnated with epoxy resin are stored at room temperature until the epoxy resin is fully cured.

[0162] Fig.9A FTIR spectra of lignin modified wood and the subsequent transparent wood are shown in comparison with natural wood. -1 The absorption peak at 1734 cm in the FTIR spectrum can be attributed to the aromatic vibrations of lignin, confirming that the in situ lignin modification and subsequent polymer infiltration maintained the aromatic framework of lignin despite the degradation of its chromophores. -1 The peak at 1235 cm -1 The peak at 1734 cm in lignin-modified wood is higher than that in natural wood. -1 The disappearance of the peak and 1235cm -1 The decrease in peak intensity indicates that the photocatalytic oxidation treatment resulted in partial dissolution / removal of hemicellulose in natural wood.

[0163] Fig. 9B The lignin content of lignin-modified wood and the subsequently formed transparent wood compared to natural wood is shown. The lignin content of natural wood and lignin-modified wood samples is about 23.5% and about 19.9%, respectively. This further confirms that most of the lignin structure is well maintained after the photocatalytic oxidation treatment. The retained lignin can act as a binder to enhance the mechanical properties of the lignin-modified wood and provide a strong wood scaffold for the subsequent polymer infiltration to form the transparent wood composite.

[0164] Figures 9C-9E Scanning electron microscope (SEM) images of natural wood, lignin-modified wood, and transparent wood are shown. Fig. 9C As shown, natural wood shows a 3D hierarchical and interconnected porous microstructure characterized by microchannels (e.g., lumens) with cross-sectional dimensions (e.g., diameter) ranging from about 15 μm to about 300 μm. This unique porous microstructure facilitates rapid penetration / diffusion of H2O2 solution within the wood microchannels and efficient UV light capture, which allows for efficient removal of light-absorbing chromophores during photocatalytic oxidation. Fig.9D As shown, the lignin-modified wood substantially retains the porous microstructure of the wood, and the cross-sectional size (e.g., diameter) of the microchannels in the lignin-modified wood is in the range of about 10 μm to about 270 μm. Fig.9E As shown, epoxy resin is able to penetrate into the pores of lignin-modified wood, thereby forming a dense and compact composite structure that helps to suppress light scattering and improve optical transmittance.

[0165] In particular, both the transparent wood formed by radial / transverse (T) cut wood (e.g., having dimensions of 70 mm×30 mm×1.5 mm) and the transparent wood formed by longitudinal (L) cut wood (e.g., having dimensions of 400 mm×110 mm×1 mm) exhibit excellent optical properties. Fig.9F The optical transmittance of natural wood and transparent wood in the range of 200-2000 nm is shown. The transparent wood along the L direction and the T direction has a high transmittance of about 90% for wavelengths in the range of 400-800 nm (inclusive). In contrast, the transmittance of natural wood in the same range is much smaller, for example, the transmittance in the L direction is <6%, and the transmittance in the T direction is <36%. Since the photocatalytic oxidation removes the light-absorbing chromophores of lignin, almost all visible light can pass through the transparent wood. Therefore, as Figure 9G As shown, for wavelengths in the range of 400-800 nm (inclusive), the absorptivity of transparent wood is close to 0%, which is much lower than that of natural wood in the same range. At the same time, the preservation of the cellulose-based microstructure enables transparent wood to have a combination of enhanced haze characteristics and high transparency. For example, Figure 9HThe light transmission haze values ​​of the transparent wood along the L direction and the T direction are shown, wherein each cut piece of the transparent wood shows a haze value ranging from about 60% to about 80% for a wavelength within the range of 400-800 nm (inclusive).

[0166] Although balsa wood was used in the above examples, transparent wood can be made from any type of hardwood or softwood. In fact, transparent wood with excellent optical transparency is also made from other woods of varying densities, notably oak and poplar, which demonstrates the universality of this approach. In addition, the transparent wood maintains the aligned channels of the original wood microstructure, which allows guiding light propagation along the channel direction and provides anisotropic optical transmittance.

[0167] As mentioned above, the retention of lignin within the transparent wood composite can enhance its mechanical properties. The mechanical properties of natural wood and transparent wood were measured in different tensile directions. The tensile strength of natural wood along the L and T directions were 24.5 MPa and 0.7 MPa, respectively, while the tensile strengths of L- and T-transparent wood samples were 46.2 MPa and 31.4 MPa, respectively (equivalent to a 1.8-fold and 44.8-fold increase in the strength of the corresponding natural wood cut pieces). Compared with natural wood (L, 0.26 MJ m -3 ; T, 0.03MJ m -3 ), the toughness of L and T transparent wood is also significantly improved, which is 0.93MJ m -3 and 1.64MJ m -3 The toughness of L transparent wood is lower than that of T transparent wood, as the elongation at break of L sample is smaller (3.4% < 7.4%). Thanks to the high mechanical strength, transparent wood is also very flexible and can be bent at angles exceeding 90° (e.g., up to 180°) without breaking.

[0168] Conventional solution-based delignification methods typically involve immersing the entire wood block in a chemical solution, which makes it difficult to bleach selective areas of the material. In contrast, surface application of a liquid oxidant in combination with UV light irradiation (e.g., brushing H2O2 onto wood) can allow for selective in situ lignin modification of designated areas of a wood sample, thereby enabling the preparation of transparent wood composites with unique predetermined patterns, independent of any underlying natural pattern in the wood. In particular, patterned transparent wood composites can be formed by selectively and precisely patterning to define lignin-modified regions and unmodified (e.g., natural lignin) regions in a continuous block, and then infiltrating the continuous block with a polymer. Within the polymer-infiltrated continuous block, the lignin-modified regions thus exhibit relatively high optical transmittance (e.g., about 90% for visible wavelengths), while the unmodified regions exhibit optical transmittance similar to that of natural wood (e.g., about 6% to about 36% for visible wavelengths).

[0169] To form the patterned transparent wood composite, H2O2 was first used as "ink" to draw the desired pattern on the surface of a natural wood sample with a brush. The wood surface was then irradiated with UV light, which turned the area below the brushed surface white. Then, epoxy resin was infiltrated into the microchannels of the lignin-modified wood to obtain a transparent wood composite with the desired pattern. For example, Fig.9I The L-transparent wood composite material 900 patterned using the above method is shown in the form of a yin-yang symbol. The lignin in portion 902 has been modified in situ to remove the chromophore therefrom and thus appears white, and the lignin in portion 904 is substantially unmodified (e.g., the natural form of lignin). The polymer permeation thus converts portion 902 to transparent, while portion 904 remains substantially opaque.

[0170] Although the above embodiments use artificial UV light sources, solar radiation can also be used as a UV light source. Of the ultraviolet light (100–400 nm) emitted by the sun, more than 95% of the wavelengths reaching the earth's surface are in the UVA range (e.g., 315–400 nm), which can effectively provide the desired photocatalytic effect. For example, using solar radiation (global solar UV index of 7-8), three large pieces of balsa wood (1 m in length) were in-situ modified with lignin after only one hour of exposure. Subsequent polymer infiltration converted the white modified wood portion into a high transparency wood composite portion.

[0171] Other embodiments of the disclosed technology

[0172] In view of the above embodiments of the disclosed subject matter, the present application discloses other examples in the clauses set forth below. It should be noted that a feature of a separate clause, or multiple features of a combined clause, and optionally, a combination with one or more features of one or more other clauses are all other examples of the content disclosed in the present application.

[0173] Article 1. A material comprising:

[0174] a continuous mass of chemically modified wood that retains the cellulose-based microstructure of the wood in its native state, infiltrated with a polymer having a refractive index that substantially matches that of cellulose and that fills the open spaces within the microstructure,

[0175] wherein the continuous block has a first portion and a second portion adjacent to the first portion;

[0176] At least one of the first portion and the second portion has been chemically modified such that a lignin signature of the first portion is different than a lignin signature of the second portion;

[0177] The first portion is substantially transparent to light having a wavelength of 600 nm, and

[0178] The second portion is translucent or opaque to light having a wavelength of 600 nm.

[0179] Clause 2. The material of any clause herein, particularly Clause 1 or an example, wherein the lignin characteristic is lignin content and the first portion has a lower lignin content than the second portion.

[0180] Clause 3. Material as herein described, in particular any one of Clauses 1 to 2 or an example, wherein the wood in its natural state is softwood.

[0181] Article 4. The material of any article herein, in particular any one of Articles 1 to 3 or an embodiment, wherein the first portion is substantially transparent to some or all wavelengths in the visible light spectrum (e.g., 380-750 nm), and the second portion is translucent or opaque to some or all wavelengths in the visible light spectrum (e.g., 380-750 nm).

[0182] Article 5. The material of any article herein, especially any article or embodiment of Articles 1 to 4, wherein the first part has a transmittance of at least 85% for light with a wavelength of 600 nm, the first part has a transmittance of at least 80% for some or all wavelengths in the visible light spectrum (e.g., 380-750 nm), the second part has a transmittance of less than or equal to 70% for some or all wavelengths in the visible light spectrum (e.g., 380-750 nm), the second part has a transmittance of less than or equal to 60% for light with a wavelength of 600 nm, or any combination of the above.

[0183] Clause 6. The material of any clause herein, in particular any one of clauses 1 to 5 or an example, wherein the extent of lignin removal in the first portion is greater than the extent of lignin removal in the second portion.

[0184] Clause 7. Material of any clause herein, in particular any one of clauses 1 to 7 or an example, wherein the first part has no more than 10% of the lignin of wood in its natural state and the second part has at least 25% (e.g., at least 35% or at least 50%) of the lignin of wood in its natural state.

[0185] Clause 8. The material of any clause herein, in particular any one of clauses 1 to 7 or an example, wherein the lignin content of the first portion is less than or equal to 3 wt%.

[0186] Clause 9. The material of any clause herein, in particular any one of clauses 1 to 8 or an example, wherein the lignin content of the first portion is less than or equal to 1 wt%.

[0187] Clause 10. The material of any clause herein, in particular any one of clauses 1 to 9 or an example, wherein the lignin content of the second part is greater than or equal to 7.5 wt%.

[0188] Clause 11. The material of any clause herein, in particular any one of clauses 1 to 10 or an example, wherein the lignin content of the second part is greater than or equal to 12.5 wt%.

[0189] Clause 12. Material of any clause herein, in particular any one of clauses 1 to 11 or an example, wherein the first part has at least 90% of the lignin of the wood in its natural state removed by chemical modification and the second part has no more than 75% of the lignin of the wood in its natural state removed by chemical modification.

[0190] Clause 13. The material of any clause herein, in particular any one of clauses 1 to 12 or an embodiment, wherein the second portion has no more than 65% (e.g., less than or equal to 50%) of the lignin of the wood in its natural state removed by chemical modification.

[0191] Clause 14. The material of any clause herein, in particular any one of clauses 1 to 13 or an embodiment, wherein the continuous block has a transmittance of no more than 20% for some or all wavelengths of light within the range of 200-400 nm, inclusive.

[0192] Clause 15. The material of any clause herein, in particular any one of clauses 1 to 14 or an example, wherein the continuous wood block exhibits a haze of at least 50% for light having a wavelength of 600 nm.

[0193] Article 16. The material of any of the articles herein, in particular any of the articles 1 to 15 or the embodiments, wherein the continuous wood block exhibits a haze of at least 60% for light having a wavelength in the range of 400-600 nm, inclusive, or the continuous wood block exhibits a haze of at least 65% for some or all wavelengths in the range of 400-600 nm, inclusive.

[0194] Clause 17. Material of any clause herein, in particular any one of Clauses 1 to 16 or an example, wherein the first portion corresponds to an earlywood region of the wood in its natural state, and the second portion corresponds to a latewood region of the wood in its natural state.

[0195] Article 18. Any material contained in any of the clauses herein, in particular any of clauses 1 to 17 or any of the examples, where:

[0196] The first portion has a first density, and the cellulose-based microstructures in the first portion have a first lumen defined by a first cell wall, the first lumen has a first average cross-sectional dimension, and the first cell wall has a first average thickness;

[0197] The second portion has a second density, and the cellulose-based microstructures in the second portion have a second lumen defined by a second cell wall, the second lumen having a second average cross-sectional dimension, the second cell wall having a second average thickness; and

[0198] The second density is greater than the first density, the first average cross-sectional size is greater than the second average cross-sectional size, the first average thickness is less than the second average thickness, or any combination of the above.

[0199] Article 19. The material of any of the articles herein, in particular any of the articles 1 to 18 or the embodiments, wherein the cellulose-based microstructure has a lumen defined by a cell wall, the lumen extending along the longitudinal growth direction of the wood in its natural state, and the cellulose nanofibers forming the cell wall also extend along the longitudinal growth direction and are substantially perpendicular to the radial direction of the wood in its natural state.

[0200] Clause 20. A material as herein described, in particular Clause 19 or an embodiment, wherein the tensile strength of a continuous mass in a substantially radial direction is at least three times the tensile strength of the wood in its natural state.

[0201] Clause 21. The material of any clause herein, in particular any one of clauses 19 to 20 or an embodiment, wherein the tensile strength of a continuous mass substantially in a radial direction is at least 20 MPa.

[0202] Clause 22. The material of any clause herein, in particular any one of clauses 19 to 21 or an embodiment, wherein the tensile strength of the continuous piece substantially along the longitudinal growth direction is at least 60 MPa.

[0203] Clause 23. The material of any clause herein, in particular any one of clauses 19 to 22 or an embodiment, wherein the tensile strength of the continuous piece substantially along the longitudinal growth direction is at least 80 MPa.

[0204] Clause 24. The material of any clause herein, in particular Clause 1 or an example, wherein the lignin characteristics include the chromophore state of the lignin, the first portion has a chromophore state that is different from the chromophore state of wood in its natural state, and the lignin in the second portion retains the chromophore state of wood in its natural state.

[0205] Clause 25. A material according to any clause herein, in particular Clause 24 or an example, wherein the altered chromophore state comprises removal of the chromophore from lignin by oxidation.

[0206] Clause 26. Material as herein described, in particular any of Clauses 24-25 or an example, wherein the wood in its natural state is a hardwood or a softwood.

[0207] Article 27. The material of any of the articles herein, in particular any of Articles 24-26 or an embodiment, wherein the first portion is substantially transparent to some or all wavelengths in the visible light spectrum (e.g., 380-750 nm), and the second portion is opaque to some or all wavelengths in the visible light spectrum (e.g., 380-750 nm).

[0208] Article 28. The material of any article herein, especially any article or embodiment of Articles 24-27, wherein the first part has a transmittance of at least 85% for light with a wavelength of 600 nm, the first part has a transmittance of at least 80% for some or all wavelengths in the visible light spectrum (e.g., 380-750 nm), the second part has a transmittance of less than or equal to 60% for some or all wavelengths in the visible light spectrum (e.g., 380-750 nm), the second part has a transmittance of less than or equal to 50% for light with a wavelength of 600 nm, or any combination of the above.

[0209] Clause 29. The material of any clause herein, in particular any one of clauses 24-28 or an embodiment, wherein the first portion has a transmittance of 90% or greater for some or all wavelengths within the range of 400-800 nm, inclusive.

[0210] Clause 30. The material of any clause herein, in particular any one of clauses 24-29 or an example, wherein both the first part and the second part have at least 70% of the lignin of wood in its natural state.

[0211] Clause 31. The material of any clause herein, in particular any one of Clauses 24-30 or an example, wherein the lignin content of the second part is greater than the lignin content of the first part.

[0212] Clause 32. The material of any clause herein, in particular any one of Clauses 24-31 or an example, wherein the lignin content of the first part, the lignin content of the second part, or the lignin content of both the first part and the second part is at least 15 wt%.

[0213] Clause 33. The material of any clause herein, in particular any one of clauses 24-32 or an example, wherein the first part and the second part have no more than 30% of the lignin of the wood in its natural state removed by chemical modification.

[0214] Clause 34. The material of any clause herein, in particular any one of clauses 24-33 or an embodiment, wherein the continuous block has a transmittance of no more than 20% for some or all wavelengths of light within the range of 200-350 nm, inclusive.

[0215] Clause 35. The material of any clause herein, in particular any one of clauses 24-34 or an embodiment, wherein the continuous block has an absorptivity of at least 80% for some or all wavelengths of light within the range of 200-350 nm, inclusive.

[0216] Clause 36. The material of any clause herein, in particular any one of clauses 24-35 or an embodiment, wherein the continuous block exhibits a haze of at least 50% for light having a wavelength of 600 nm.

[0217] Clause 37. The material of any clause herein, in particular any one of Clauses 24-36 or an embodiment, wherein the continuous block exhibits a haze of at least 60% for some or all wavelengths of light in the range of 400-800 nm, inclusive, or the continuous block exhibits a haze of at least 65% for some or all wavelengths of light in the range of 400-800 nm, inclusive.

[0218] Clause 38. The material of any clause herein, in particular any one of Clauses 24-37 or an embodiment, wherein the first portion and the second portion form a predetermined pattern that is independent of the underlying cellulose-based microstructure of the wood in its natural state.

[0219] Article 39. The material of any of the articles herein, in particular any of Articles 24 to 38 or an embodiment, wherein the cellulose-based microstructure has a lumen defined by a cell wall, the lumen extending along the longitudinal growth direction of the wood in its natural state, and the cellulose nanofibers forming the cell wall also extend along the longitudinal growth direction and are substantially perpendicular to the radial direction of the wood in its natural state.

[0220] Article 40. Any material contained in any of the Articles herein, in particular Article 39 or the Examples, where:

[0221] The continuous block has a tensile strength in a substantially radial direction of at least 40 times the tensile strength of the wood in its natural state;

[0222] The continuous block has a tensile strength substantially in the longitudinal growth direction of at least 1.5 times the tensile strength of the wood in its natural state;

[0223] The continuous block has a tensile strength of at least 25 MPa substantially in the radial direction;

[0224] The continuous block has a tensile strength of at least 40 MPa substantially in the longitudinal growth direction; or

[0225] Any combination of the above.

[0226] Article 41. A material comprising:

[0227] Chemically modifying a portion of wood so that the chromophores of the lignin in the wood in its natural state are altered or removed,

[0228] wherein the portion retains at least 70% of the lignin within the wood in its natural state and the cellulose-based microstructure of the wood in its natural state.

[0229] Item 42. A material as herein described, in particular Item 41 or an example, wherein the lignin content of the portion is at least 15 wt%.

[0230] Clause 43. The material of any clause herein, in particular any one of Clauses 41-42 or an example, wherein the portion has at least 80% of the lignin of wood in its natural state.

[0231] Article 44. Any material contained in any of the clauses herein, in particular any of clauses 41 to 43 or any of the examples, wherein:

[0232] Each of the three orthogonal dimensions of the portion is greater than or equal to 0.5 mm;

[0233] Each of the three orthogonal dimensions of the portion is greater than or equal to 1 cm;

[0234] At least two of the three orthogonal dimensions of the portion are greater than or equal to 10 cm;

[0235] At least one of the three orthogonal dimensions of the portion is greater than or equal to 20 cm; or

[0236] Any combination of the above.

[0237] Article 45. Material of any of the articles herein, in particular any of Articles 41-44 or an embodiment, wherein the portion comprises a continuous block of wood.

[0238] Article 46. Any material contained in any of the clauses herein, in particular any of clauses 41 to 44 or any of the examples, wherein:

[0239] The portion includes a first portion of a continuous block;

[0240] The material includes a second portion of the continuous block adjacent to the first portion; and

[0241] The lignin in the second portion retains the chromophore state of wood in its natural state.

[0242] Clause 47. The material of any clause herein, in particular any one of Clauses 45-46 or an embodiment, wherein the continuous wood block consists essentially of wood.

[0243] Clause 48. The material of any clause herein, in particular any one of clauses 41-47 or an embodiment, wherein the portion has a reflectivity of 90% or greater for some or all wavelengths of light within the range of 400-800 nm, inclusive.

[0244] Article 49. The material of any article herein, in particular any one of Articles 41-48 or an example, wherein the color of the part is substantially white.

[0245] Article 50. The material of any of the articles herein, in particular any of Articles 41-48 or an embodiment, wherein the portion further comprises a polymer that permeates the cellulose-based microstructure, the refractive index of the polymer substantially matching the refractive index of the cellulose and filling the open spaces within the microstructure, and the portion is substantially transparent to light having a wavelength of 600 nm.

[0246] Clause 51. The material of any clause herein, particularly Clause 50 or an embodiment, wherein the portion is substantially transparent to some or all wavelengths within the visible light spectrum (eg, 380-750 nm).

[0247] Article 52. Any material in any of the clauses herein, in particular any of clauses 50-51 or the examples, where the part:

[0248] For light with a wavelength of 600 nm, the transmittance is at least 80%;

[0249] The transmittance is 90% or greater for some or all wavelengths of light within the range of 400-800 nm, inclusive;

[0250] For some or all wavelengths of light within the range of 200-350 nm, inclusive, the transmittance does not exceed 20%;

[0251] The absorbance is at least 80% for some or all of the wavelengths of light within the range of 200-350 nm, inclusive;

[0252] For light having a wavelength of 600 nm, the haze is at least 65%;

[0253] The haze is at least 50% (e.g., at least 60% or at least 65%) for some or all wavelengths of light in the range of 400-800 nm, inclusive; or

[0254] Any combination of the above.

[0255] Clause 53. The material of any clause herein, in particular any one of Clauses 50-52 or an embodiment, wherein the portion consists essentially of wood and infiltrated polymer.

[0256] Article 54. A method comprising:

[0257] chemically treating a continuous piece of wood for a first time to remove lignin from a first portion and a second portion within the continuous piece while substantially maintaining the cellulose-based microstructure of the wood, the first portion being adjacent to the second portion, the first time being selected such that at least 90% of the lignin of the wood in the first portion is removed and no more than 75% (e.g., less than or equal to 65%, or less than or equal to 50%) of the lignin in the second portion is removed; and

[0258] infiltrating the continuous mass with a polymer having a refractive index substantially matching the refractive index of cellulose to fill open spaces within the retained cellulose-based microstructures of the first portion and the second portion,

[0259] Wherein, after the penetration, the first portion is substantially transparent to light having a wavelength of 600 nm, and the second portion is semi-transparent to light having a wavelength of 600 nm.

[0260] Clause 55. The method of any clause herein, in particular Clause 54 or an example, wherein the wood is softwood.

[0261] Article 56. A method according to any of the articles herein, in particular any of Articles 54-55 or an embodiment, wherein, after penetration, the first part has a transmittance of at least 85% for light with a wavelength of 600 nm, the first part has a transmittance of at least 80% for some or all wavelengths in the visible light spectrum (e.g., 380-750 nm), the second part has a transmittance of less than or equal to 70% for some or all wavelengths in the visible light spectrum (e.g., 380-750 nm), the second part has a transmittance of less than or equal to 60% for light with a wavelength of 600 nm, or any combination of the above.

[0262] Clause 57. The method of any clause herein, in particular any one of Clauses 54-56 or an embodiment, wherein after said treating, the lignin content of said first portion is less than or equal to 3 wt%.

[0263] Clause 58. The method of any clause herein, in particular any one of Clauses 54-57 or an embodiment, wherein, after said treating, the lignin content of said first portion is less than or equal to 1 wt%.

[0264] Clause 59. The method of any clause herein, in particular any one of Clauses 54-58 or an embodiment, wherein, after said treating, the lignin content of the second portion is greater than or equal to 7.5 wt%.

[0265] Clause 60. The method of any clause herein, in particular any one of Clauses 54-59 or an embodiment, wherein, after said treating, the lignin content of the second portion is greater than or equal to 12.5 wt%.

[0266] Clause 61. The method of any clause herein, in particular any one of Clauses 54-60 or an embodiment, wherein the first portion corresponds to an earlywood region of the wood in its natural state, and the second portion corresponds to a latewood region of the wood in its natural state.

[0267] Clause 62. The method of any clause herein, in particular any one of clauses 54-61 or an embodiment, wherein the chemical treatment comprises a sodium chlorite (NaClO2) solution.

[0268] Clause 63. The method of any clause herein, in particular any one of clauses 54-62 or an embodiment, wherein the chemical treatment comprises a solution of sodium chlorite (NaClO2) and acetic acid.

[0269] Clause 64. The method of any clause herein, in particular any clause or embodiment of Clause 63, wherein the solution is boiled during the treatment.

[0270] Clause 65. The method of any clause herein, in particular any one of Clauses 54-64 or an embodiment, wherein the first time is less than or substantially equal to 5 hours.

[0271] Clause 66. The method of any clause herein, in particular any one of Clauses 54-65 or an embodiment, wherein the first time does not exceed 2 hours.

[0272] Clause 67. The method of any clause herein, in particular any one of clauses 54-66 or an embodiment, wherein the infiltrating comprises:

[0273] immersing the continuous mass in a liquid polymer or polymer precursor;

[0274] applying a vacuum to cause the liquid polymer or polymer precursor to flow into the cellulose-based microstructure; and

[0275] The liquid polymer is dried or the precursor is polymerized to form a solid polymer in situ within the microstructure of the continuous mass.

[0276] Clause 68. The method of any clause herein, in particular Clause 67 or an embodiment, wherein the infiltrating further comprises pressing the continuous mass during drying or polymerization.

[0277] Clause 69. The method of any clause herein, in particular any one of clauses 54-68 or an example, wherein the polymer comprises an epoxy resin.

[0278] Article 70. A method comprising:

[0279] applying a first volume of liquid oxidant to an exterior surface of a portion of the continuous wood block; and

[0280] During or after applying, exposing the portion of the continuous wood block to ultraviolet (UV) radiation,

[0281] wherein the chromophores of the lignin within the portion are chemically oxidized and removed in situ by UV exposure in the presence of a liquid oxidant, and

[0282] After exposure, the cellulose-based microstructure of the wood and at least 70% of the lignin in the part before application is retained.

[0283] Clause 71. The method of any clause herein, in particular Clause 70 or an embodiment, wherein the liquid oxidant comprises a hydrogen peroxide (H2O2) solution.

[0284] Clause 72. The method of any clause herein, in particular Clause 71 or an example, wherein the concentration of hydrogen peroxide in the solution is at least 30 wt%.

[0285] Clause 73. The method of any clause herein, in particular any one of Clauses 70-72 or an embodiment, wherein, after exposure, the portion has a lignin content of at least 15 wt%.

[0286] Clause 74. The method of any clause herein, in particular any one of clauses 70-73 or an embodiment, wherein the outer surface of the portion has a surface area and the first volume has a volume of at least 800 ml / m 2 of the surface area.

[0287] Clause 75. The method of any clause herein, in particular any one of Clauses 70-74 or an embodiment, wherein the portion has a thickness in a direction perpendicular to the outer surface and the first volume is at least 125 ml / square meter of surface area / 0.1 mm thickness.

[0288] Clause 76. The method of any clause herein, in particular any one of Clauses 70-75 or an embodiment, wherein the first volume is less than 1.5 times the volume of the portion, or the first volume is between 1 and 5 times the volume of the portion, inclusive.

[0289] Clause 77. The method of any clause herein, in particular any one of clauses 70-76 or an embodiment, wherein prior to or simultaneously with said applying, a second volume of alkali is applied to the outer surface of said portion of the continuous wood block.

[0290] Clause 78. The method of any clause herein, in particular Clause 77 or an example, wherein the second volume is less than or equal to 20% of the first volume.

[0291] Clause 79. The method of any clause herein, in particular any one of Clauses 77-78 or an embodiment, wherein the second volume does not exceed 3 ml.

[0292] Clause 80. The method of any clause herein, in particular any one of clauses 77-79 or an embodiment, wherein the base comprises sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), calcium hydroxide (Ca(OH)2), or any combination of the foregoing.

[0293] Clause 81. The method of any clause herein, in particular any one of clauses 77-80 or an example, wherein the concentration of the base in the solution is at least 10 wt%.

[0294] Clause 82. The method of any clause herein, in particular any one of clauses 70-81 or an embodiment, wherein the applying comprises immersing the continuous block in the first volume of the liquid oxidant.

[0295] Clause 83. The method of any clause herein, in particular any one of clauses 70-81 or an embodiment, wherein the applying comprises applying directly to the outer surface without impregnating the continuous mass.

[0296] Clause 84. The method of any clause herein, in particular Clause 83 or an embodiment, wherein the applying comprises a plurality of sub-applications to achieve the first volume.

[0297] Clause 85. The method of any clause herein, in particular any one of Clauses 83-84 or an embodiment, wherein the direct application comprises brushing, spraying, rolling, or any combination thereof.

[0298] Clause 86. A method as herein described, in particular any of Clauses 83-85 or an embodiment, wherein said applying comprises applying said first volume to said outer surface in a predetermined pattern without applying any liquid oxidant to a second portion of the continuous block adjacent said portion.

[0299] Clause 87. The method of any clause herein, in particular Clause 86 or an embodiment, wherein, after exposing, the lignin content of the second portion is greater than the lignin content of the portion.

[0300] Clause 88. The method of any clause herein, in particular any one of Clauses 86-87 or an embodiment, wherein, after exposure, the portion is substantially white and the second portion is non-white.

[0301] Clause 89. The method of any clause herein, in particular any one of clauses 86-88 or an embodiment, further comprising defining the boundaries of the predetermined pattern by providing a hydrophobic material on the outer surface prior to applying.

[0302] Clause 90. The method of any clause herein, in particular Clause 89 or an example, wherein the hydrophobic material comprises petrolatum.

[0303] Clause 91. The method of any clause herein, in particular any one of clauses 70-90 or an embodiment, wherein the exposing comprises irradiating the portion using a mask having a predetermined pattern without irradiating a second portion of a continuous block adjacent to the portion.

[0304] Clause 92. The method of any clause herein, in particular Clause 91 or an embodiment, wherein, after exposure, the lignin content of the second portion is greater than the lignin content of the portion.

[0305] Clause 93. The method of any clause herein, in particular any one of Clauses 91-92 or an embodiment, wherein, after exposure, the portion is substantially white and the second portion is non-white.

[0306] Article 94. The method of any of the clauses herein, in particular any of clauses 70-93 or an embodiment, further comprising:

[0307] After said exposing, infiltrating said continuous mass with a polymer to fill open spaces within said portion of the retained cellulose-based microstructure, said polymer having a refractive index substantially matching that of cellulose,

[0308] Wherein, after said penetration, said portion is substantially transparent to light having a wavelength of 600 nm.

[0309] Clause 95. The method of any clause herein, particularly Clause 94 or an embodiment, wherein the infiltrating comprises:

[0310] immersing the continuous mass in a liquid polymer or polymer precursor;

[0311] applying a vacuum to cause the liquid polymer or polymer precursor to flow into the cellulose-based microstructure; and

[0312] The liquid polymer is dried or the precursor is polymerized to form a solid polymer in situ within the microstructure of the continuous mass.

[0313] Clause 96. The method of any clause herein, in particular any one of Clauses 94-95 or an embodiment, wherein the polymer comprises an epoxy resin.

[0314] Clause 97. A method as herein described, in particular any of Clauses 94-96 or an embodiment, wherein, after infiltration, the portion:

[0315] At least 90% transmittance for light with a wavelength of 600nm;

[0316] At least 80% transmittance for some or all wavelengths of light within the range of 400-800 nm, inclusive;

[0317] For some or all wavelengths of light within the range of 200-350 nm, inclusive, no more than 20% transmittance;

[0318] At least 80% absorptivity for some or all wavelengths of light within the range of 200-350 nm, inclusive;

[0319] At least 50% haze for light with a wavelength of 600 nm;

[0320] A haze of at least 65% for some or all wavelengths of light within the range of 400-800 nm, inclusive; or

[0321] Any combination of the above.

[0322] Clause 98. The method of any clause herein, in particular any one of clauses 70-97 or an embodiment, wherein the UV radiation is from an artificial light source that produces at least 20 W of UVA band radiation.

[0323] Clause 99. The method of any clause herein, in particular any one of clauses 70-97 or an embodiment, wherein the UV radiation is sunlight having an ultraviolet index (UVI) of at least 5.

[0324] Clause 100. The method of any clause herein, in particular any one of clauses 70-99 or an embodiment, wherein the exposure time is 2 hours or less.

[0325] Clause 101. The method of any clause herein, in particular any one of clauses 70-99 or an example, wherein the exposure time is 1 hour or less.

[0326] Article 102. A method comprising:

[0327] (a) Photocatalytic oxidation of a portion of a continuous wood block to chemically modify native lignin in situ within the portion to remove its chromophores while retaining its bulk aromatic framework.

[0328] Article 103. A method as herein provided, in particular Article 102 or an embodiment, wherein:

[0329] Prior to (a), the portion has a first content of lignin therein;

[0330] After (a), the portion has a second amount of lignin therein; and

[0331] The second content is at least 70% of the first content.

[0332] Clause 104. The method of any clause herein, in particular Clause 103 or an example, wherein the second content of lignin is at least 15 wt%.

[0333] Clause 105. The method of any clause herein, in particular any one of clauses 102-104 or an embodiment, wherein, after (a), the color of the portion is substantially white.

[0334] Clause 106. The method of any clause herein, in particular any one of clauses 102-105 or an embodiment, wherein, after (a), the portion has a reflectivity of at least 85% for light having a wavelength in the range of 400-800 nm, inclusive.

[0335] Article 107. The method of any of the clauses herein, particularly any of clauses 102-106 or an embodiment, further comprising:

[0336] (b) Following (a), infiltrating the continuous wood block with an index matching polymer to render the portion substantially transparent to visible light.

[0337] Article 108. A method as herein provided, particularly Article 107 or an example, wherein, after (b):

[0338] The portion has a transmittance of at least 85% for some or all wavelengths of light within the range of 400-800 nm, inclusive;

[0339] The portion has a haze of at least 65% for some or all wavelengths of light within the range of 400-800 nm, inclusive;

[0340] Or both.

[0341] Clause 109. The method of any clause herein, in particular any one of Clauses 102-108 or an embodiment, wherein the photocatalytic oxidation comprises a combination of hydrogen peroxide and ultraviolet radiation.

[0342] Clause 110. The method of any clause herein, in particular Clause 109 or an embodiment, wherein the hydrogen peroxide is applied to the outer surface of the portion without immersing the continuous block in the solution.

[0343] Clause 111. The method of any clause herein, in particular any one of Clauses 102-110 or an embodiment, wherein another portion of the continuous block is not subjected to photocatalytic oxidation during (a) such that the portion and the another portion form a predetermined pattern.

[0344] Clause 112. The method of any clause herein, particularly Clause 111 or an embodiment, wherein, during (a), no more than one of hydrogen peroxide and ultraviolet radiation is applied to the other portion.

[0345] Clause 113. A material formed by a method as described herein, particularly any one of Clauses 54-112 or an example.

[0346] Article 114. A material according to any of the articles herein, in particular any of the articles 1 to 53 and 113 or an example, which is suitable for use as a building material or a structural material.

[0347] in conclusion

[0348] for Figure 1A-9I Any feature shown or described in Section 1-114 may be used in conjunction with any feature shown or described in Section 1-114. Figure 1A-9ICombined with any other features shown or described in Items 1-114 to provide materials, structures, methods, devices, and embodiments not otherwise shown or specifically described herein. All features described herein are independent of each other and can be used in combination with any other features described herein, except where structurally impossible.

[0349] In view of the many possible embodiments to which the principles of the disclosed technology can be applied, it should be recognized that the embodiments shown are only preferred examples and should not be considered to limit the scope of the disclosed technology. Rather, the scope is defined by the following claims. Therefore, we claim the scope and spirit of all such claims.

Claims

1. A material comprising: Chemically modifying a portion of wood so that the chromophores of the lignin in the wood in its natural state are altered or removed, wherein the portion retains at least 70% of the lignin of the wood in its native state and the cellulose-based microstructure of the wood in its native state.

2. The material according to claim 1, wherein the lignin content of the portion is at least 15 wt%.

3. The material of claim 1, wherein the portion has at least 80% of the lignin of wood in its natural state.

4. The material of claim 1, wherein each of three orthogonal dimensions of the portion is greater than or equal to 0.5 mm.

5. The material of claim 1, wherein at least two of the three orthogonal dimensions of the portion are greater than or equal to 10 cm.

6. The material of claim 1, wherein the portion comprises an integral body of continuous wood block.

7. The material according to claim 1, wherein: The portion includes a first portion of a continuous block; The material includes a second portion of the continuous block adjacent to the first portion; and The lignin in the second portion retains the chromophore state of wood in its natural state.

8. The material of claim 7, wherein the continuous block consists essentially of wood.

9. The material of claim 1, wherein the portion has a reflectivity of 90% or more with respect to light having a wavelength within the range of 400-800 nm, inclusive.

10. The material of claim 1, wherein the portion is substantially white in color.

11. The material of claim 1 , wherein the portion further comprises a polymer that permeates the cellulose-based microstructure, the polymer having a refractive index substantially matching that of the cellulose and filling open spaces within the microstructure, and the portion has a transmittance of at least 80% for light having a wavelength of 600 nm.

12. The material according to claim 11, wherein the portion has a transmittance of 90% or more for light having a wavelength in the range of 400-800 nm, inclusive.

13. The material of claim 11, wherein the portion has a transmittance of no more than 20% for light having a wavelength within the range of 200-350 nm, inclusive.

14. The material of claim 11, wherein the portion has an absorptivity of at least 80% for light having a wavelength in the range of 200-350 nm, inclusive.

15. The material of claim 11, wherein the portion has a haze of at least 50% for light having a wavelength of 600 nm.

16. The material of claim 11, wherein the portion consists essentially of wood and infiltrated polymer.

17. The material of any one of claims 11-16, wherein the polymer comprises an epoxy resin.

18. A method comprising: (a) applying a first volume of a liquid oxidant to an outer surface of a portion of the continuous wood block; and (b) during or after (a), chemically oxidizing and removing chromophores of lignin in the portion in the presence of a liquid oxidant, wherein after (b), the cellulose-based microstructure of the wood and at least 70% of the lignin in the portion before (a) are retained.

19. The method of claim 18, wherein (b) comprises exposing the portion of the continuous wood block to ultraviolet (UV) radiation such that chromophores of lignin within the portion are chemically oxidized and removed in situ by UV exposure in the presence of a liquid oxidant.

20. The method of claim 19, wherein the exposing comprises irradiating the portion using a mask having a predetermined pattern without irradiating a second portion of the continuous block adjacent to the portion.

21. The method according to claim 20, wherein: After exposure, the second portion has a lignin content greater than the lignin content of the portion.

22. The method according to claim 20, wherein: After exposure, the portion is substantially white and the second portion is non-white.

23. The method of claim 18, wherein the liquid oxidant comprises a solution of hydrogen peroxide (H2O2).

24. The method of claim 23, wherein the concentration of hydrogen peroxide in the solution is at least 30 wt%.

25. The method of claim 18, wherein: After (b), the portion has a lignin content of at least 15 wt%.

26. The method of claim 18, wherein the outer surface of the portion has a surface area and the first volume has a surface area of ​​at least 800 ml / m 2 The surface area.

27. The method of claim 18, wherein the portion has a thickness in a direction perpendicular to the outer surface, and the first volume is at least 125 ml / m2 surface area / 0.1 mm thickness.

28. The method of claim 18, wherein the first volume is between 1 and 5 times, inclusive, the volume of the portion.

29. The method of claim 18, wherein prior to or simultaneously with the application of (a), a second volume of alkali is applied to the outer surface of the portion of the continuous wood block.

30. The method of claim 29, wherein the second volume is less than or equal to 20% of the first volume.

31. The method of claim 29, wherein the second volume does not exceed 3 ml.

32. The method of claim 29, wherein the base comprises sodium hydroxide (NaOH), potassium hydroxide (KOH), ammonium hydroxide (NH4OH), calcium hydroxide (Ca(OH)2), or any combination of the foregoing.

33. The method of claim 29, wherein the concentration of the base in the solution is at least 10 wt%.

34. The method of claim 18, wherein the applying of (a) comprises immersing the continuous block in the first volume of the liquid oxidant.

35. The method of claim 18, wherein the applying of (a) comprises applying directly to an outer surface without impregnating the continuous mass.

36. The method of claim 35, wherein the applying of (a) comprises a plurality of sub-applications to achieve the first volume.

37. The method of claim 35, wherein the direct application comprises brushing, spraying, rolling, or any combination thereof.

38. The method of claim 18, wherein said applying of (a) comprises applying said first volume to said exterior surface in a predetermined pattern without applying any liquid oxidant to a second portion of the continuous wood block adjacent said portion.

39. The method of claim 38, wherein: After (b), the second portion has a lignin content greater than the lignin content of the portion.

40. The method of claim 38, wherein: After (b), the first portion is substantially white and the second portion is non-white.

41. The method of claim 38, further comprising, prior to the applying of (a), defining boundaries of the predetermined pattern by providing a hydrophobic material on the outer surface.

42. The method of claim 41, wherein the hydrophobic material comprises petrolatum.

43. The method according to any one of claims 18 to 42, further comprising: subsequent to said (b), infiltrating said continuous mass with a polymer to fill open spaces within said portion of the retained cellulose-based microstructure, said polymer having a refractive index substantially matching that of cellulose, wherein, after the penetration, the portion has a transmittance of at least 80% for light having a wavelength of 600 nm.

44. The method of claim 43, wherein the infiltrating comprises: immersing the continuous mass in a liquid polymer or polymer precursor; applying a vacuum to cause the liquid polymer or polymer precursor to flow into the cellulose-based microstructure; and The liquid polymer is dried or the precursor is polymerized to form a solid polymer in situ within the microstructure of the continuous mass.

45. The method of claim 43, wherein the polymer comprises an epoxy resin.

46. ​​The method of claim 43, wherein: After said penetration, said portion has a transmittance of at least 90% for light having a wavelength in the range of 400-800 nm, inclusive.

47. The method of claim 43, wherein: After said penetration, said portion has a transmittance of not more than 20% for light having a wavelength within the range of 200-350 nm, inclusive.

48. The method of claim 43, wherein: After said penetration, said portion has an absorptivity of at least 80% for light having a wavelength in the range of 200-350 nm, inclusive.

49. The method of claim 43, wherein: After the penetration, the portion has a haze of at least 50% with respect to light having a wavelength of 600 nm.

50. The method of claim 18, wherein (b) comprises exposing the portion of the continuous wood block to ultraviolet (UV) radiation from an artificial light source that produces at least 20 W of UVA band radiation.

51. The method of claim 50, wherein the exposure is for 2 hours or less.

52. The method of claim 18, wherein (b) comprises exposing the portion of the continuous wood block to sunlight having an ultraviolet index (UVI) of at least 5.

53. The method of claim 52, wherein the exposure is for 1 hour or less.

54. A method comprising: (a) Photocatalytic oxidation of a portion of a continuous wood block to chemically modify native lignin in situ within the portion to remove its chromophores while retaining its bulk aromatic framework.

55. The method of claim 54, wherein: Prior to (a), the portion has a first content of lignin therein; After (a), the portion has a second amount of lignin therein; and The second content is at least 70% of the first content.

56. The method of claim 55, wherein the second content is at least 15 wt%.

57. The method of claim 54, wherein: After (a), the portion is substantially white in color.

58. The method of claim 54, wherein: After (a), the portion has a reflectivity of at least 85% for light having a wavelength in the range of 400-800 nm, inclusive.

59. The method of claim 54, further comprising: (b), after (a), the continuous wood block is infiltrated with an index matching polymer, wherein, after (b), the portion has a transmittance of at least 85% for light having a wavelength in the range of 400-800 nm, inclusive.

60. The method of claim 59, wherein: After (b), the portion has a haze of at least 65% for light having a wavelength in the range of 400-800 nm, inclusive.

61. The method of claim 54, wherein the photocatalytic oxidation comprises a combination of hydrogen peroxide and ultraviolet radiation.

62. A method according to claim 61, wherein the hydrogen peroxide is applied to the outer surface of the part without immersing the continuous block in the solution.

63. The method of claim 61, wherein another portion of the continuous block is not subjected to photocatalytic oxidation during (a) such that the portion and the another portion form a predetermined pattern.

64. The method of claim 63, wherein: During (a), no more than one of hydrogen peroxide and ultraviolet radiation is applied to the other portion.

65. A material comprising: A continuous block of chemically modified wood infiltrated with a polymer, wherein the continuous block has a first portion and a second portion, the first portion having a lignin content lower than the lignin content of the second portion, the first part and the second part are from the same tree, and The first portion has a transmittance of at least 85% for light having a wavelength of 600 nm, and the second portion has a transmittance of less than or equal to 60% for light having a wavelength of 600 nm.

66. The material of claim 65, wherein the first portion has a lignin content less than or equal to 3 wt%.

67. The material of claim 65, wherein the second portion has a lignin content greater than or equal to 7.5 wt%.

68. The material of claim 65, wherein the first portion corresponds to an earlywood region of wood in its natural state, and the second portion corresponds to a latewood region of wood in its natural state.

69. The material of any one of claims 65-68, wherein the polymer comprises an epoxy resin.

Citation Information

Patent Citations

  • Transparent wood composite, systems and method of fabrication

    WO2017136714A1